Atomic structure of the entire mammalian mitochondrial complex i - Fiedorczuk, Karol; Letts, James A; Degliesposti, Gianluca; Kaszuba, Karol; Skehel, Mark; Sazanov, Leonid A (Nature)
Mitochondrial complex I (also known as NADH:ubiquinone oxidoreductase) contributes to cellular energy production by transferring electrons from NADH to ubiquinone coupled to proton translocation across the membrane. It is the largest protein assembly of the respiratory chain with a total mass of 970 kilodaltons. Here we present a nearly complete atomic structure of ovine (Ovis aries) mitochondrial complex I at 3.9 Å resolution, solved by cryo-electron microscopy with cross-linking and mass-spectrometry mapping experiments. All 14 conserved core subunits and 31 mitochondria-specific supernumerary subunits are resolved within the L-shaped molecule. The hydrophilic matrix arm comprises flavin mononucleotide and 8 iron-sulfur clusters involved in electron transfer, and the membrane arm contains 78 transmembrane helices, mostly contributed by antiporter-like subunits involved in proton translocation. Supernumerary subunits form an interlinked, stabilizing shell around the conserved core. Tightly bound lipids (including cardiolipins) further stabilize interactions between the hydrophobic subunits. Subunits with possible regulatory roles contain additional cofactors, NADPH and two phosphopantetheine molecules, which are shown to be involved in inter-subunit interactions. We observe two different conformations of the complex, which may be related to the conformationally driven coupling mechanism and to the active-deactive transition of the enzyme. Our structure provides insight into the mechanism, assembly, maturation and dysfunction of mitochondrial complex I, and allows detailed molecular analysis of disease-causing mutations.

Discrete abstraction of multiaffine systems - Kong, Hui; Bartocci, Ezio; Bogomolov, Sergiy; Grosu, Radu; Henzinger, Thomas A; Jiang, Yu; Schilling, Christian
Many biological systems can be modeled as multiaffine hybrid systems. Due to the nonlinearity of multiaffine systems, it is difficult to verify their properties of interest directly. A common strategy to tackle this problem is to construct and analyze a discrete overapproximation of the original system. However, the conservativeness of a discrete abstraction significantly determines the level of confidence we can have in the properties of the original system. In this paper, in order to reduce the conservativeness of a discrete abstraction, we propose a new method based on a sufficient and necessary decision condition for computing discrete transitions between states in the abstract system. We assume the state space partition of a multiaffine system to be based on a set of multivariate polynomials. Hence, a rectangular partition defined in terms of polynomials of the form (xi − c) is just a simple case of multivariate polynomial partition, and the new decision condition applies naturally. We analyze and demonstrate the improvement of our method over the existing methods using some examples.

On the complexity of scrypt and proofs of space in the parallel random oracle model - Alwen, Joel F; Chen, Binyi; Kamath Hosdurg, Chethan; Kolmogorov, Vladimir; Pietrzak, Krzysztof Z; Tessaro, Stefano
We study the time-and memory-complexities of the problem of computing labels of (multiple) randomly selected challenge-nodes in a directed acyclic graph. The w-bit label of a node is the hash of the labels of its parents, and the hash function is modeled as a random oracle. Specific instances of this problem underlie both proofs of space [Dziembowski et al. CRYPTO’15] as well as popular memory-hard functions like scrypt. As our main tool, we introduce the new notion of a probabilistic parallel entangled pebbling game, a new type of combinatorial pebbling game on a graph, which is closely related to the labeling game on the same graph. As a first application of our framework, we prove that for scrypt, when the underlying hash function is invoked n times, the cumulative memory complexity (CMC) (a notion recently introduced by Alwen and Serbinenko (STOC’15) to capture amortized memory-hardness for parallel adversaries) is at least Ω(w · (n/ log(n))2). This bound holds for adversaries that can store many natural functions of the labels (e.g., linear combinations), but still not arbitrary functions thereof. We then introduce and study a combinatorial quantity, and show how a sufficiently small upper bound on it (which we conjecture) extends our CMC bound for scrypt to hold against arbitrary adversaries. We also show that such an upper bound solves the main open problem for proofs-of-space protocols: namely, establishing that the time complexity of computing the label of a random node in a graph on n nodes (given an initial kw-bit state) reduces tightly to the time complexity for black pebbling on the same graph (given an initial k-node pebbling).

The architecture of respiratory supercomplexes - Letts, James A; Fiedorczuk, Karol; Sazanov, Leonid A (Nature)
Mitochondrial electron transport chain complexes are organized into supercomplexes responsible for carrying out cellular respiration. Here we present three architectures of mammalian (ovine) supercomplexes determined by cryo-electron microscopy. We identify two distinct arrangements of supercomplex CICIII 2 CIV (the respirasome) - a major 'tight' form and a minor 'loose' form (resolved at the resolution of 5.8 Å and 6.7 Å, respectively), which may represent different stages in supercomplex assembly or disassembly. We have also determined an architecture of supercomplex CICIII 2 at 7.8 Å resolution. All observed density can be attributed to the known 80 subunits of the individual complexes, including 132 transmembrane helices. The individual complexes form tight interactions that vary between the architectures, with complex IV subunit COX7a switching contact from complex III to complex I. The arrangement of active sites within the supercomplex may help control reactive oxygen species production. To our knowledge, these are the first complete architectures of the dominant, physiologically relevant state of the electron transport chain.

Standard security does imply security against selective opening for markov distributions - Fuchsbauer, Georg; Heuer, Felix; Kiltz, Eike; Pietrzak, Krzysztof Z
About three decades ago it was realized that implementing private channels between parties which can be adaptively corrupted requires an encryption scheme that is secure against selective opening attacks. Whether standard (IND-CPA) security implies security against selective opening attacks has been a major open question since. The only known reduction from selective opening to IND-CPA security loses an exponential factor. A polynomial reduction is only known for the very special case where the distribution considered in the selective opening security experiment is a product distribution, i.e., the messages are sampled independently from each other. In this paper we give a reduction whose loss is quantified via the dependence graph (where message dependencies correspond to edges) of the underlying message distribution. In particular, for some concrete distributions including Markov distributions, our reduction is polynomial.

Endosomal interactions during root hair growth - Von Wangenheim, Daniel; Rosero, Amparo; Komis, George; Šamajová, Olga; Ovečka, Miroslav; Voigt, Boris; Šamaj, Jozef (Frontiers in Plant Science)
The dynamic localization of endosomal compartments labeled with targeted fluorescent protein tags is routinely followed by time lapse fluorescence microscopy approaches and single particle tracking algorithms. In this way trajectories of individual endosomes can be mapped and linked to physiological processes as cell growth. However, other aspects of dynamic behavior including endosomal interactions are difficult to follow in this manner. Therefore, we characterized the localization and dynamic properties of early and late endosomes throughout the entire course of root hair formation by means of spinning disc time lapse imaging and post-acquisition automated multitracking and quantitative analysis. Our results show differential motile behavior of early and late endosomes and interactions of late endosomes that may be specified to particular root hair domains. Detailed data analysis revealed a particular transient interaction between late endosomes—termed herein as dancing-endosomes—which is not concluding to vesicular fusion. Endosomes preferentially located in the root hair tip interacted as dancing-endosomes and traveled short distances during this interaction. Finally, sizes of early and late endosomes were addressed by means of super-resolution structured illumination microscopy (SIM) to corroborate measurements on the spinning disc. This is a first study providing quantitative microscopic data on dynamic spatio-temporal interactions of endosomes during root hair tip growth.

Computation of cubical Steenrod squares - Krcál, Marek; Pilarczyk, Pawel
Bitmap images of arbitrary dimension may be formally perceived as unions of m-dimensional boxes aligned with respect to a rectangular grid in ℝm. Cohomology and homology groups are well known topological invariants of such sets. Cohomological operations, such as the cup product, provide higher-order algebraic topological invariants, especially important for digital images of dimension higher than 3. If such an operation is determined at the level of simplicial chains [see e.g. González-Díaz, Real, Homology, Homotopy Appl, 2003, 83-93], then it is effectively computable. However, decomposing a cubical complex into a simplicial one deleteriously affects the efficiency of such an approach. In order to avoid this overhead, a direct cubical approach was applied in [Pilarczyk, Real, Adv. Comput. Math., 2015, 253-275] for the cup product in cohomology, and implemented in the ChainCon software package [http://www.pawelpilarczyk.com/chaincon/]. We establish a formula for the Steenrod square operations [see Steenrod, Annals of Mathematics. Second Series, 1947, 290-320] directly at the level of cubical chains, and we prove the correctness of this formula. An implementation of this formula is programmed in C++ within the ChainCon software framework. We provide a few examples and discuss the effectiveness of this approach. One specific application follows from the fact that Steenrod squares yield tests for the topological extension problem: Can a given map A → Sd to a sphere Sd be extended to a given super-complex X of A? In particular, the ROB-SAT problem, which is to decide for a given function f: X → ℝm and a value r > 0 whether every g: X → ℝm with ∥g - f ∥∞ ≤ r has a root, reduces to the extension problem.

Long non-coding RNAs display higher natural expression variation than protein-coding genes in healthy humans - Kornienko, Aleksandra; Dotter, Christoph; Guenzl, Philipp; Gisslinger, Heinz; Gisslinger, Bettina; Cleary, Ciara; Kralovics, Robert; Pauler, Florian; Barlow, Denise (Genome Biology)
Background: Long non-coding RNAs (lncRNAs) are increasingly implicated as gene regulators and may ultimately be more numerous than protein-coding genes in the human genome. Despite large numbers of reported lncRNAs, reference annotations are likely incomplete due to their lower and tighter tissue-specific expression compared to mRNAs. An unexplored factor potentially confounding lncRNA identification is inter-individual expression variability. Here, we characterize lncRNA natural expression variability in human primary granulocytes. Results: We annotate granulocyte lncRNAs and mRNAs in RNA-seq data from 10 healthy individuals, identifying multiple lncRNAs absent from reference annotations, and use this to investigate three known features (higher tissue-specificity, lower expression, and reduced splicing efficiency) of lncRNAs relative to mRNAs. Expression variability was examined in seven individuals sampled three times at 1- or more than 1-month intervals. We show that lncRNAs display significantly more inter-individual expression variability compared to mRNAs. We confirm this finding in two independent human datasets by analyzing multiple tissues from the GTEx project and lymphoblastoid cell lines from the GEUVADIS project. Using the latter dataset we also show that including more human donors into the transcriptome annotation pipeline allows identification of an increasing number of lncRNAs, but minimally affects mRNA gene number. Conclusions: A comprehensive annotation of lncRNAs is known to require an approach that is sensitive to low and tight tissue-specific expression. Here we show that increased inter-individual expression variability is an additional general lncRNA feature to consider when creating a comprehensive annotation of human lncRNAs or proposing their use as prognostic or disease markers.

Cortical flow-driven shapes of nonadherent cells - Callan Jones, Andrew; Ruprecht, Verena; Wieser, Stefan; Heisenberg, Carl-Philipp J; Voituriez, Raphaël (Physical Review Letters)
Nonadherent polarized cells have been observed to have a pearlike, elongated shape. Using a minimal model that describes the cell cortex as a thin layer of contractile active gel, we show that the anisotropy of active stresses, controlled by cortical viscosity and filament ordering, can account for this morphology. The predicted shapes can be determined from the flow pattern only; they prove to be independent of the mechanism at the origin of the cortical flow, and are only weakly sensitive to the cytoplasmic rheology. In the case of actin flows resulting from a contractile instability, we propose a phase diagram of three-dimensional cell shapes that encompasses nonpolarized spherical, elongated, as well as oblate shapes, all of which have been observed in experiment.

Extending the dynamic range of transcription factor action by translational regulation - Sokolowski, Thomas R; Walczak, Aleksandra; Bialek, William; Tkacik, Gasper (Physical Review E Statistical Nonlinear and Soft Matter Physics)
A crucial step in the regulation of gene expression is binding of transcription factor (TF) proteins to regulatory sites along the DNA. But transcription factors act at nanomolar concentrations, and noise due to random arrival of these molecules at their binding sites can severely limit the precision of regulation. Recent work on the optimization of information flow through regulatory networks indicates that the lower end of the dynamic range of concentrations is simply inaccessible, overwhelmed by the impact of this noise. Motivated by the behavior of homeodomain proteins, such as the maternal morphogen Bicoid in the fruit fly embryo, we suggest a scheme in which transcription factors also act as indirect translational regulators, binding to the mRNA of other regulatory proteins. Intuitively, each mRNA molecule acts as an independent sensor of the input concentration, and averaging over these multiple sensors reduces the noise. We analyze information flow through this scheme and identify conditions under which it outperforms direct transcriptional regulation. Our results suggest that the dual role of homeodomain proteins is not just a historical accident, but a solution to a crucial physics problem in the regulation of gene expression.

The role of recombination in evolutionary rescue - Uecker, Hildegard; Hermisson, Joachim (Genetics)
How likely is it that a population escapes extinction through adaptive evolution? The answer to this question is of great relevance in conservation biology, where we aim at species’ rescue and the maintenance of biodiversity, and in agriculture and medicine, where we seek to hamper the emergence of pesticide or drug resistance. By reshuffling the genome, recombination has two antagonistic effects on the probability of evolutionary rescue: It generates and it breaks up favorable gene combinations. Which of the two effects prevails depends on the fitness effects of mutations and on the impact of stochasticity on the allele frequencies. In this article, we analyze a mathematical model for rescue after a sudden environmental change when adaptation is contingent on mutations at two loci. The analysis reveals a complex nonlinear dependence of population survival on recombination. We moreover find that, counterintuitively, a fast eradication of the wild type can promote rescue in the presence of recombination. The model also shows that two-step rescue is not unlikely to happen and can even be more likely than single-step rescue (where adaptation relies on a single mutation), depending on the circumstances.

ROTUNDA3 function in plant development by phosphatase 2A-mediated regulation of auxin transporter recycling - Karampelias, Michael; Neyt, Pia; De Groeve, Steven; Aesaert, Stijn; Coussens, Griet; Rolčík, Jakub; Bruno, Leonardo; De Winne, Nancy; Van Minnebruggen, Annemie; Van Montagu, Marc; Ponce, Maria; Micol, José; et al. (PNAS)
The shaping of organs in plants depends on the intercellular flow of the phytohormone auxin, of which the directional signaling is determined by the polar subcellular localization of PIN-FORMED (PIN) auxin transport proteins. Phosphorylation dynamics of PIN proteins are affected by the protein phosphatase 2A (PP2A) and the PINOID kinase, which act antagonistically to mediate their apical-basal polar delivery. Here, we identified the ROTUNDA3 (RON3) protein as a regulator of the PP2A phosphatase activity in Arabidopsis thaliana. The RON3 gene was map-based cloned starting from the ron3-1 leaf mutant and found to be a unique, plant-specific gene coding for a protein with high and dispersed proline content. The ron3-1 and ron3-2 mutant phenotypes [i.e., reduced apical dominance, primary root length, lateral root emergence, and growth; increased ectopic stages II, IV, and V lateral root primordia; decreased auxin maxima in indole-3-acetic acid (IAA)-treated root apical meristems; hypergravitropic root growth and response; increased IAA levels in shoot apices; and reduced auxin accumulation in root meristems] support a role for RON3 in auxin biology. The affinity-purified PP2A complex with RON3 as bait suggested that RON3 might act in PIN transporter trafficking. Indeed, pharmacological interference with vesicle trafficking processes revealed that single ron3-2 and double ron3-2 rcn1 mutants have altered PIN polarity and endocytosis in specific cells. Our data indicate that RON3 contributes to auxin-mediated development by playing a role in PIN recycling and polarity establishment through regulation of the PP2A complex activity.

Imaging of electric and magnetic fields near plasmonic nanowires - Kabakova, Irina; De Hoogh, Anouk; Van Der Wel, Ruben; Wulf, Matthias; Le Feber, Boris; Kuipers, Laurens (Scientific Reports)
Near-field imaging is a powerful tool to investigate the complex structure of light at the nanoscale. Recent advances in near-field imaging have indicated the possibility for the complete reconstruction of both electric and magnetic components of the evanescent field. Here we study the electro-magnetic field structure of surface plasmon polariton waves propagating along subwavelength gold nanowires by performing phase- and polarization-resolved near-field microscopy in collection mode. By applying the optical reciprocity theorem, we describe the signal collected by the probe as an overlap integral of the nanowire's evanescent field and the probe's response function. As a result, we find that the probe's sensitivity to the magnetic field is approximately equal to its sensitivity to the electric field. Through rigorous modeling of the nanowire mode as well as the aperture probe response function, we obtain a good agreement between experimentally measured signals and a numerical model. Our findings provide a better understanding of aperture-based near-field imaging of the nanoscopic plasmonic and photonic structures and are helpful for the interpretation of future near-field experiments.

Game-theoretic models identify useful principles for peer collaboration in online learning platforms - Pandey, Vineet; Chatterjee, Krishnendu (Proceedings of the ACM Conference on Computer Supported Cooperative Work)
To facilitate collaboration in massive online classrooms, instructors must make many decisions. For instance, the following parameters need to be decided when designing a peer-feedback system where students review each others' essays: the number of students each student must provide feedback to, an algorithm to map feedback providers to receivers, constraints that ensure students do not become free-riders (receiving feedback but not providing it), the best times to receive feedback to improve learning etc. While instructors can answer these questions by running experiments or invoking past experience, game-theoretic models with data from online learning platforms can identify better initial designs for further improvements. As an example, we explore the design space of a peer feedback system by modeling it using game theory. Our simulations show that incentivizing students to provide feedback requires the value obtained from receiving a feedback to exceed the cost of providing it by a large factor (greater than 7). Furthermore, hiding feedback from low-effort students incentivizes them to provide more feedback.

Chimera proteins with affinity for membranes and microtubule tips polarize in the membrane of fission yeast cells - Recouvreux, Pierre; Sokolowski, Thomas R; Grammoustianou, Aristea; Tenwolde, Pieter; Dogterom, Marileen (PNAS)
Cell polarity refers to a functional spatial organization of proteins that is crucial for the control of essential cellular processes such as growth and division. To establish polarity, cells rely on elaborate regulation networks that control the distribution of proteins at the cell membrane. In fission yeast cells, a microtubule-dependent network has been identified that polarizes the distribution of signaling proteins that restricts growth to cell ends and targets the cytokinetic machinery to the middle of the cell. Although many molecular components have been shown to play a role in this network, it remains unknown which molecular functionalities are minimally required to establish a polarized protein distribution in this system. Here we show that a membrane-binding protein fragment, which distributes homogeneously in wild-type fission yeast cells, can be made to concentrate at cell ends by attaching it to a cytoplasmic microtubule end-binding protein. This concentration results in a polarized pattern of chimera proteins with a spatial extension that is very reminiscent of natural polarity patterns in fission yeast. However, chimera levels fluctuate in response to microtubule dynamics, and disruption of microtubules leads to disappearance of the pattern. Numerical simulations confirm that the combined functionality of membrane anchoring and microtubule tip affinity is in principle sufficient to create polarized patterns. Our chimera protein may thus represent a simple molecular functionality that is able to polarize the membrane, onto which additional layers of molecular complexity may be built to provide the temporal robustness that is typical of natural polarity patterns.

Information processing in living systems - Tkacik, Gasper; Bialek, William (Annual Review of Condensed Matter Physics)
Life depends as much on the flow of information as on the flow of energy. Here we review the many efforts to make this intuition precise. Starting with the building blocks of information theory, we explore examples where it has been possible to measure, directly, the flow of information in biological networks, or more generally where information-theoretic ideas have been used to guide the analysis of experiments. Systems of interest range from single molecules (the sequence diversity in families of proteins) to groups of organisms (the distribution of velocities in flocks of birds), and all scales in between. Many of these analyses are motivated by the idea that biological systems may have evolved to optimize the gathering and representation of information, and we review the experimental evidence for this optimization, again across a wide range of scales.

Determining physical properties of the cell cortex - Saha, Arnab; Nishikawa, Masatoshi; Behrndt, Martin; Heisenberg, Carl-Philipp J; Julicher, Frank; Grill, Stephan (Biophysical Journal)
Actin and myosin assemble into a thin layer of a highly dynamic network underneath the membrane of eukaryotic cells. This network generates the forces that drive cell- and tissue-scale morphogenetic processes. The effective material properties of this active network determine large-scale deformations and other morphogenetic events. For example, the characteristic time of stress relaxation (the Maxwell time τM) in the actomyosin sets the timescale of large-scale deformation of the cortex. Similarly, the characteristic length of stress propagation (the hydrodynamic length λ) sets the length scale of slow deformations, and a large hydrodynamic length is a prerequisite for long-ranged cortical flows. Here we introduce a method to determine physical parameters of the actomyosin cortical layer in vivo directly from laser ablation experiments. For this we investigate the cortical response to laser ablation in the one-cell-stage Caenorhabditis elegans embryo and in the gastrulating zebrafish embryo. These responses can be interpreted using a coarse-grained physical description of the cortex in terms of a two-dimensional thin film of an active viscoelastic gel. To determine the Maxwell time τM, the hydrodynamic length λ, the ratio of active stress ζΔμ, and per-area friction γ, we evaluated the response to laser ablation in two different ways: by quantifying flow and density fields as a function of space and time, and by determining the time evolution of the shape of the ablated region. Importantly, both methods provide best-fit physical parameters that are in close agreement with each other and that are similar to previous estimates in the two systems. Our method provides an accurate and robust means for measuring physical parameters of the actomyosin cortical layer. It can be useful for investigations of actomyosin mechanics at the cellular-scale, but also for providing insights into the active mechanics processes that govern tissue-scale morphogenesis.

TWISTED DWARF1 mediates the action of auxin transport inhibitors on actin cytoskeleton dynamics - Zhu, Jinsheng; Bailly, Aurélien; Zwiewka, Marta; Sovero, Valpuri; Di Donato, Martin; Ge, Pei; Oehri, Jacqueline; Aryal, Bibek; Hao, Pengchao; Linnert, Miriam; Burgardt, Noelia; Lücke, Christian; et al. (Plant Cell)
Plant growth and architecture is regulated by the polar distribution of the hormone auxin. Polarity and flexibility of this process is provided by constant cycling of auxin transporter vesicles along actin filaments, coordinated by a positive auxinactin feedback loop. Both polar auxin transport and vesicle cycling are inhibited by synthetic auxin transport inhibitors, such as 1-Nnaphthylphthalamic acid (NPA), counteracting the effect of auxin; however, underlying targets and mechanisms are unclear. Using NMR, we map the NPA binding surface on the Arabidopsis thaliana ABCB chaperone TWISTED DWARF1 (TWD1).We identify ACTIN7 as a relevant, although likely indirect, TWD1 interactor, and show TWD1-dependent regulation of actin filament organization and dynamics and that TWD1 is required for NPA-mediated actin cytoskeleton remodeling. The TWD1-ACTIN7 axis controls plasma membrane presence of efflux transporters, and as a consequence act7 and twd1 share developmental and physiological phenotypes indicative of defects in auxin transport. These can be phenocopied by NPA treatment or by chemical actin (de)stabilization. We provide evidence that TWD1 determines downstreamlocations of auxin efflux transporters by adjusting actin filament debundling and dynamizing processes and mediating NPA action on the latter. This function appears to be evolutionary conserved since TWD1 expression in budding yeast alters actin polarization and cell polarity and provides NPA sensitivity.

Inducing a map on homology from a correspondence - Harker, Shaun; Kokubu, Hiroshi; Mischaikow, Konstantin; Pilarczyk, Pawel (Proceedings of the American Mathematical Society)
We study the homomorphism induced in homology by a closed correspondence between topological spaces, using projections from the graph of the correspondence to its domain and codomain. We provide assumptions under which the homomorphism induced by an outer approximation of a continuous map coincides with the homomorphism induced in homology by the map. In contrast to more classical results we do not require that the projection to the domain have acyclic preimages. Moreover, we show that it is possible to retrieve correct homological information from a correspondence even if some data is missing or perturbed. Finally, we describe an application to combinatorial maps that are either outer approximations of continuous maps or reconstructions of such maps from a finite set of data points.

Uniform expansivity outside a critical neighborhood in the quadratic family - Golmakani, Ali; Luzzatto, Stefano; Pilarczyk, Pawel (Experimental Mathematics)
We use rigorous numerical techniques to compute a lower bound for the exponent of expansivity outside a neighborhood of the critical point for thousands of intervals of parameter values in the quadratic family. We first compute a radius of the critical neighborhood outside which the map is uniformly expanding. This radius is taken as small as possible, yet large enough for our numerical procedure to succeed in proving that the expansivity exponent outside this neighborhood is positive. Then, for each of the intervals, we compute a lower bound for this expansivity exponent, valid for all the parameters in that interval. We illustrate and study the distribution of the radii and the expansivity exponents. The results of our computations are mathematically rigorous. The source code of the software and the results of the computations are made publicly available at http://www.pawelpilarczyk.com/quadratic/.

Down syndrome cell adhesion molecule 1: Testing for a role in insect immunity, behaviour and reproduction - Peuß, Robert; Wensing, Kristina; Woestmann, Luisa; Eggert, Hendrik; Milutinovic, Barbara; Sroka, Marlene; Scharsack, Jörn; Kurtz, Joachim; Armitage, Sophie (Royal Society Open Science)
Down syndrome cell adhesion molecule 1 (Dscam1) has widereaching and vital neuronal functions although the role it plays in insect and crustacean immunity is less well understood. In this study, we combine different approaches to understand the roles that Dscam1 plays in fitness-related contexts in two model insect species. Contrary to our expectations, we found no short-term modulation of Dscam1 gene expression after haemocoelic or oral bacterial exposure in Tribolium castaneum, or after haemocoelic bacterial exposure in Drosophila melanogaster. Furthermore, RNAi-mediated Dscam1 knockdown and subsequent bacterial exposure did not reduce T. castaneum survival. However, Dscam1 knockdown in larvae resulted in adult locomotion defects, as well as dramatically reduced fecundity in males and females. We suggest that Dscam1 does not always play a straightforward role in immunity, but strongly influences behaviour and fecundity. This study takes a step towards understanding more about the role of this intriguing gene from different phenotypic perspectives.

From stateflow simulation to verified implementation: A verification approach and a real-time train controller design - Jiang, Yu; Yang, Yixiao; Liu, Han; Kong, Hui; Gu, Ming; Sun, Jiaguang; Sha, Lui
Simulink is widely used for model driven development (MDD) of industrial software systems. Typically, the Simulink based development is initiated from Stateflow modeling, followed by simulation, validation and code generation mapped to physical execution platforms. However, recent industrial trends have raised the demands of rigorous verification on safety-critical applications, which is unfortunately challenging for Simulink. In this paper, we present an approach to bridge the Stateflow based model driven development and a well- defined rigorous verification. First, we develop a self- contained toolkit to translate Stateflow model into timed automata, where major advanced modeling features in Stateflow are supported. Taking advantage of the strong verification capability of Uppaal, we can not only find bugs in Stateflow models which are missed by Simulink Design Verifier, but also check more important temporal properties. Next, we customize a runtime verifier for the generated nonintrusive VHDL and C code of Stateflow model for monitoring. The major strength of the customization is the flexibility to collect and analyze runtime properties with a pure software monitor, which opens more opportunities for engineers to achieve high reliability of the target system compared with the traditional act that only relies on Simulink Polyspace. We incorporate these two parts into original Stateflow based MDD seamlessly. In this way, safety-critical properties are both verified at the model level, and at the consistent system implementation level with physical execution environment in consideration. We apply our approach on a train controller design, and the verified implementation is tested and deployed on a real hardware platform.

A central limit theorem for products of random matrices and GOE statistics for the Anderson model on long boxes - Sadel, Christian; Virág, Bálint (Communications in Mathematical Physics)
We consider products of random matrices that are small, independent identically distributed perturbations of a fixed matrix (Formula presented.). Focusing on the eigenvalues of (Formula presented.) of a particular size we obtain a limit to a SDE in a critical scaling. Previous results required (Formula presented.) to be a (conjugated) unitary matrix so it could not have eigenvalues of different modulus. From the result we can also obtain a limit SDE for the Markov process given by the action of the random products on the flag manifold. Applying the result to random Schrödinger operators we can improve some results by Valko and Virag showing GOE statistics for the rescaled eigenvalue process of a sequence of Anderson models on long boxes. In particular, we solve a problem posed in their work.

DRACULA2 is a dynamic nucleoporin with a role in regulating the shade avoidance syndrome in Arabidopsis - Gallemi Rovira, Marcal; Galstyan, Anahit; Paulišić, Sandi; Then, Christiane; Ferrández Ayela, Almudena; Lorenzo Orts, Laura; Roig Villanova, Irma; Wang, Xuewen; Micol, José; Ponce, Maria; Devlin, Paul; Martínez García, Jaime (Development)
When plants grow in close proximity basic resources such as light can become limiting. Under such conditions plants respond to anticipate and/or adapt to the light shortage, a process known as the shade avoidance syndrome (SAS). Following genetic screening using a shade-responsive luciferase reporter line (PHYB:LUC), we identified DRACULA2 (DRA2), which encodes an Arabidopsis homolog of mammalian nucleoporin 98, a component of the nuclear pore complex (NPC). DRA2, together with other nucleoporins, participates positively in the control of the hypocotyl elongation response to plant proximity, a role that can be considered dependent on the nucleocytoplasmic transport of macromolecules (i.e. is transport dependent). In addition, our results reveal a specific role for DRA2 in controlling shade-induced gene expression. We suggest that this novel regulatory role of DRA2 is transport independent and that it might rely on its dynamic localization within and outside of the NPC. These results provide mechanistic insights in to how SAS responses are rapidly established by light conditions. They also indicate that nucleoporins have an active role in plant signaling.

Bogolubov–Hartree–Fock theory for strongly interacting fermions in the low density limit - Bräunlich, Gerhard; Hainzl, Christian; Seiringer, Robert (Mathematical Physics, Analysis and Geometry)
We consider the Bogolubov–Hartree–Fock functional for a fermionic many-body system with two-body interactions. For suitable interaction potentials that have a strong enough attractive tail in order to allow for two-body bound states, but are otherwise sufficiently repulsive to guarantee stability of the system, we show that in the low-density limit the ground state of this model consists of a Bose–Einstein condensate of fermion pairs. The latter can be described by means of the Gross–Pitaevskii energy functional.

The dual of the space of interactions in neural network models - De Martino, Daniele (International Journal of Modern Physics C)
In this work, the Gardner problem of inferring interactions and fields for an Ising neural network from given patterns under a local stability hypothesis is addressed under a dual perspective. By means of duality arguments, an integer linear system is defined whose solution space is the dual of the Gardner space and whose solutions represent mutually unstable patterns. We propose and discuss Monte Carlo methods in order to find and remove unstable patterns and uniformly sample the space of interactions thereafter. We illustrate the problem on a set of real data and perform ensemble calculation that shows how the emergence of phase dominated by unstable patterns can be triggered in a nonlinear discontinuous way.

Long-time behavior of a finite volume discretization for a fourth order diffusion equation - Maas, Jan; Matthes, Daniel (Nonlinearity)
We consider a non-standard finite-volume discretization of a strongly non-linear fourth order diffusion equation on the d-dimensional cube, for arbitrary . The scheme preserves two important structural properties of the equation: the first is the interpretation as a gradient flow in a mass transportation metric, and the second is an intimate relation to a linear Fokker-Planck equation. Thanks to these structural properties, the scheme possesses two discrete Lyapunov functionals. These functionals approximate the entropy and the Fisher information, respectively, and their dissipation rates converge to the optimal ones in the discrete-to-continuous limit. Using the dissipation, we derive estimates on the long-time asymptotics of the discrete solutions. Finally, we present results from numerical experiments which indicate that our discretization is able to capture significant features of the complex original dynamics, even with a rather coarse spatial resolution.

Sorting motifs involved in the trafficking and localization of the PIN1 auxin efflux carrier - Sancho Andrés, Gloria; Soriano Ortega, Esther; Gao, Caiji; Bernabé Orts, Joan; Narasimhan, Madhumitha; Müller, Anna; Tejos, Ricardo; Jiang, Liwen; Friml, Jirí; Aniento, Fernando; Marcote, Maria (Plant Physiology)
n contrast with the wealth of recent reports about the function of μ-adaptins and clathrin adaptor protein (AP) complexes, there is very little information about the motifs that determine the sorting of membrane proteins within clathrin-coated vesicles in plants. Here, we investigated putative sorting signals in the large cytosolic loop of the Arabidopsis (Arabidopsis thaliana) PIN-FORMED1 (PIN1) auxin transporter, which are involved in binding μ-adaptins and thus in PIN1 trafficking and localization. We found that Phe-165 and Tyr-280, Tyr-328, and Tyr-394 are involved in the binding of different μ-adaptins in vitro. However, only Phe-165, which binds μA(μ2)- and μD(μ3)-adaptin, was found to be essential for PIN1 trafficking and localization in vivo. The PIN1:GFP-F165A mutant showed reduced endocytosis but also localized to intracellular structures containing several layers of membranes and endoplasmic reticulum (ER) markers, suggesting that they correspond to ER or ER-derived membranes. While PIN1:GFP localized normally in a μA (μ2)-adaptin mutant, it accumulated in big intracellular structures containing LysoTracker in a μD (μ3)-adaptin mutant, consistent with previous results obtained with mutants of other subunits of the AP-3 complex. Our data suggest that Phe-165, through the binding of μA (μ2)- and μD (μ3)-adaptin, is important for PIN1 endocytosis and for PIN1 trafficking along the secretory pathway, respectively.

Mapping the subcellular mechanical properties of live cells in tissues with fluorescence emission-Brillouin imaging - Elsayad, Kareem; Werner, Stephanie; Gallemi Rovira, Marcal; Kong, Jixiang; Guajardo, Edmundo; Zhang, Lijuan; Jaillais, Yvon; Greb, Thomas; Belkhadir, Youssef (Science Signaling)
Extracellular matrices (ECMs) are central to the advent of multicellular life, and their mechanical propertiesare modulated by and impinge on intracellular signaling pathways that regulate vital cellular functions. High spatial-resolution mapping of mechanical properties in live cells is, however, extremely challenging. Thus, our understanding of how signaling pathways process physiological signals to generate appropriate mechanical responses is limited. We introduce fluorescence emission-Brillouin scattering imaging (FBi), a method for the parallel and all-optical measurements of mechanical properties and fluorescence at the submicrometer scale in living organisms. Using FBi, we showed thatchanges in cellular hydrostatic pressure and cytoplasm viscoelasticity modulate the mechanical signatures of plant ECMs. We further established that the measured "stiffness" of plant ECMs is symmetrically patternedin hypocotyl cells undergoing directional growth. Finally, application of this method to Arabidopsis thaliana with photoreceptor mutants revealed that red and far-red light signals are essential modulators of ECM viscoelasticity. By mapping the viscoelastic signatures of a complex ECM, we provide proof of principlefor the organism-wide applicability of FBi for measuring the mechanical outputs of intracellular signaling pathways. As such, our work has implications for investigations of mechanosignaling pathways and developmental biology.

Neural oscillations as a signature of efficient coding in the presence of synaptic delays - Chalk, Matthew J; Gutkin, Boris; Denève, Sophie (eLife)
Cortical networks exhibit ‘global oscillations’, in which neural spike times are entrained to an underlying oscillatory rhythm, but where individual neurons fire irregularly, on only a fraction of cycles. While the network dynamics underlying global oscillations have been well characterised, their function is debated. Here, we show that such global oscillations are a direct consequence of optimal efficient coding in spiking networks with synaptic delays and noise. To avoid firing unnecessary spikes, neurons need to share information about the network state. Ideally, membrane potentials should be strongly correlated and reflect a ‘prediction error’ while the spikes themselves are uncorrelated and occur rarely. We show that the most efficient representation is when: (i) spike times are entrained to a global Gamma rhythm (implying a consistent representation of the error); but (ii) few neurons fire on each cycle (implying high efficiency), while (iii) excitation and inhibition are tightly balanced. This suggests that cortical networks exhibiting such dynamics are tuned to achieve a maximally efficient population code.

Plant hormones in interactions with the environment - Benková, Eva (Plant Molecular Biology)
Plants are continuously exposed to a myriad of external signals such as fluctuating nutrients availability, drought, heat, cold, high salinity, or pathogen/pest attacks that can severely affect their development, growth, and fertility. As sessile organisms, plants must therefore be able to sense and rapidly react to these external inputs, activate efficient responses, and adjust development to changing conditions. In recent years, significant progress has been made towards understanding the molecular mechanisms underlying the intricate and complex communication between plants and the environment. It is now becoming increasingly evident that hormones have an important regulatory role in plant adaptation and defense mechanisms.

Nonexistence of large nuclei in the liquid drop model - Frank, Rupert; Killip, Rowan; Nam, Phan (Letters in Mathematical Physics)
We give a simplified proof of the nonexistence of large nuclei in the liquid drop model and provide an explicit bound. Our bound is within a factor of 2.3 of the conjectured value and seems to be the first quantitative result.

Immune memory in invertebrates - Milutinovic, Barbara; Kurtz, Joachim (Seminars in Immunology)

Steering cell migration by alternating blebs and actin-rich protrusions - Diz Muñoz, Alba; Romanczuk, Pawel; Yu, Weimiao; Bergert, Martin; Ivanovitch, Kenzo; Salbreux, Guillame; Heisenberg, Carl-Philipp J; Paluch, Ewa (BMC Biology)
Background: High directional persistence is often assumed to enhance the efficiency of chemotactic migration. Yet, cells in vivo usually display meandering trajectories with relatively low directional persistence, and the control and function of directional persistence during cell migration in three-dimensional environments are poorly understood. Results: Here, we use mesendoderm progenitors migrating during zebrafish gastrulation as a model system to investigate the control of directional persistence during migration in vivo. We show that progenitor cells alternate persistent run phases with tumble phases that result in cell reorientation. Runs are characterized by the formation of directed actin-rich protrusions and tumbles by enhanced blebbing. Increasing the proportion of actin-rich protrusions or blebs leads to longer or shorter run phases, respectively. Importantly, both reducing and increasing run phases result in larger spatial dispersion of the cells, indicative of reduced migration precision. A physical model quantitatively recapitulating the migratory behavior of mesendoderm progenitors indicates that the ratio of tumbling to run times, and thus the specific degree of directional persistence of migration, are critical for optimizing migration precision. Conclusions: Together, our experiments and model provide mechanistic insight into the control of migration directionality for cells moving in three-dimensional environments that combine different protrusion types, whereby the proportion of blebs to actin-rich protrusions determines the directional persistence and precision of movement by regulating the ratio of tumbling to run times.

Lateral root emergence in Arabidopsis is dependent on transcription factor LBD29 regulation of auxin influx carrier LAX3 - Porco, Silvana; Larrieu, Antoine; Du, Yujuan; Gaudinier, Allison; Goh, Tatsuaki; Swarup, Kamal; Swarup, Ranjan; Kuempers, Britta; Bishopp, Anthony; Lavenus, Julien; Casimiro, Ilda; Hill, Kristine; et al. (Development)
Lateral root primordia (LRP) originate from pericycle stem cells located deep within parental root tissues. LRP emerge through overlying root tissues by inducing auxin-dependent cell separation and hydraulic changes in adjacent cells. The auxin-inducible auxin influx carrier LAX3 plays a key role concentrating this signal in cells overlying LRP. Delimiting LAX3 expression to two adjacent cell files overlying new LRP is crucial to ensure that auxin-regulated cell separation occurs solely along their shared walls. Multiscale modeling has predicted that this highly focused pattern of expression requires auxin to sequentially induce auxin efflux and influx carriers PIN3 and LAX3, respectively. Consistent with model predictions, we report that auxin-inducible LAX3 expression is regulated indirectly by AUXIN RESPONSE FACTOR 7 (ARF7). Yeast one-hybrid screens revealed that the LAX3 promoter is bound by the transcription factor LBD29, which is a direct target for regulation by ARF7. Disrupting auxin-inducible LBD29 expression or expressing an LBD29-SRDX transcriptional repressor phenocopied the lax3 mutant, resulting in delayed lateral root emergence. We conclude that sequential LBD29 and LAX3 induction by auxin is required to coordinate cell separation and organ emergence.

Generalized offsetting of planar structures using skeletons - Held, Martin; Huber, Stefan; Palfrader, Peter (Computer-Aided Design and Applications)
We study different means to extend offsetting based on skeletal structures beyond the well-known constant-radius and mitered offsets supported by Voronoi diagrams and straight skeletons, for which the orthogonal distance of offset elements to their respective input elements is constant and uniform over all input elements. Our main contribution is a new geometric structure, called variable-radius Voronoi diagram, which supports the computation of variable-radius offsets, i.e., offsets whose distance to the input is allowed to vary along the input. We discuss properties of this structure and sketch a prototype implementation that supports the computation of variable-radius offsets based on this new variant of Voronoi diagrams.

Optogenetically blocking sharp wave ripple events in sleep does not interfere with the formation of stable spatial representation in the CA1 area of the hippocampus - Kovács, Krisztián; O'Neill, Joseph; Schönenberger, Philipp; Penttonen, Markku; Rangel Guerrero, Dámaris K; Csicsvari, Jozsef L (PLoS One)
During hippocampal sharp wave/ripple (SWR) events, previously occurring, sensory inputdriven neuronal firing patterns are replayed. Such replay is thought to be important for plasticity- related processes and consolidation of memory traces. It has previously been shown that the electrical stimulation-induced disruption of SWR events interferes with learning in rodents in different experimental paradigms. On the other hand, the cognitive map theory posits that the plastic changes of the firing of hippocampal place cells constitute the electrophysiological counterpart of the spatial learning, observable at the behavioral level. Therefore, we tested whether intact SWR events occurring during the sleep/rest session after the first exploration of a novel environment are needed for the stabilization of the CA1 code, which process requires plasticity. We found that the newly-formed representation in the CA1 has the same level of stability with optogenetic SWR blockade as with a control manipulation that delivered the same amount of light into the brain. Therefore our results suggest that at least in the case of passive exploratory behavior, SWR-related plasticity is dispensable for the stability of CA1 ensembles.

Distribution and structure of synapses on medial vestibular nuclear neurons targeted by cerebellar flocculus purkinje cells and vestibular nerve in mice: Light and electron microscopy studies - Matsuno, Hitomi; Kudoh, Moeko; Watakabe, Akiya; Yamamori, Tetsuo; Shigemoto, Ryuichi; Nagao, Soichi (PLoS One)
Adaptations of vestibulo-ocular and optokinetic response eye movements have been studied as an experimental model of cerebellum-dependent motor learning. Several previous physiological and pharmacological studies have consistently suggested that the cerebellar flocculus (FL) Purkinje cells (P-cells) and the medial vestibular nucleus (MVN) neurons targeted by FL (FL-targeted MVN neurons) may respectively maintain the memory traces of short- and long-term adaptation. To study the basic structures of the FL-MVN synapses by light microscopy (LM) and electron microscopy (EM), we injected green florescence protein (GFP)-expressing lentivirus into FL to anterogradely label the FL P-cell axons in C57BL/6J mice. The FL P-cell axonal boutons were distributed in the magnocellular MVN and in the border region of parvocellular MVN and prepositus hypoglossi (PrH). In the magnocellular MVN, the FL-P cell axons mainly terminated on somata and proximal dendrites. On the other hand, in the parvocellular MVN/PrH, the FL P-cell axonal synaptic boutons mainly terminated on the relatively small-diameter (< 1 μm) distal dendrites of MVN neurons, forming symmetrical synapses. The majority of such parvocellular MVN/PrH neurons were determined to be glutamatergic by immunocytochemistry and in-situ hybridization of GFP expressing transgenic mice. To further examine the spatial relationship between the synapses of FL P-cells and those of vestibular nerve on the neurons of the parvocellular MVN/ PrH, we added injections of biotinylated dextran amine into the semicircular canal and anterogradely labeled vestibular nerve axons in some mice. The MVN dendrites receiving the FL P-cell axonal synaptic boutons often closely apposed vestibular nerve synaptic boutons in both LM and EM studies. Such a partial overlap of synaptic boutons of FL P-cell axons with those of vestibular nerve axons in the distal dendrites of MVN neurons suggests that inhibitory synapses of FL P-cells may influence the function of neighboring excitatory synapses of vestibular nerve in the parvocellular MVN/PrH neurons.

Atomistic determinants of co-enzyme Q reduction at the Qi-site of the cytochrome bc1 complex - Postila, Pekka; Kaszuba, Karol; Kuleta, Patryk; Vattulainen, Ilpo; Sarewicz, Marcin; Osyczka, Artur; Róg, Tomasz (Scientific Reports)
The cytochrome (cyt) bc 1 complex is an integral component of the respiratory electron transfer chain sustaining the energy needs of organisms ranging from humans to bacteria. Due to its ubiquitous role in the energy metabolism, both the oxidation and reduction of the enzyme's substrate co-enzyme Q has been studied vigorously. Here, this vast amount of data is reassessed after probing the substrate reduction steps at the Q i-site of the cyt bc 1 complex of Rhodobacter capsulatus using atomistic molecular dynamics simulations. The simulations suggest that the Lys251 side chain could rotate into the Q i-site to facilitate binding of half-protonated semiquinone-a reaction intermediate that is potentially formed during substrate reduction. At this bent pose, the Lys251 forms a salt bridge with the Asp252, thus making direct proton transfer possible. In the neutral state, the lysine side chain stays close to the conserved binding location of cardiolipin (CL). This back-and-forth motion between the CL and Asp252 indicates that Lys251 functions as a proton shuttle controlled by pH-dependent negative feedback. The CL/K/D switching, which represents a refinement to the previously described CL/K pathway, fine-tunes the proton transfer process. Lastly, the simulation data was used to formulate a mechanism for reducing the substrate at the Q i-site.

Danger-associated peptide signaling in Arabidopsis requires clathrin - Ortiz Morea, Fausto; Savatin, Daniel; Dejonghe, Wim; Kumar, Rahul; Luo, Yu; Adamowski, Maciek; Van Begin, Jos; Dressano, Keini; De Oliveira, Guilherme; Zhao, Xiuyang; Lu, Qing; Madder, Annemieke; et al. (PNAS)
The Arabidopsis thaliana endogenous elicitor peptides (AtPeps) are released into the apoplast after cellular damage caused by pathogens or wounding to induce innate immunity by direct binding to the membrane-localized leucine-rich repeat receptor kinases, PEP RECEPTOR1 (PEPR1) and PEPR2. Although the PEPR-mediated signaling components and responses have been studied extensively, the contributions of the subcellular localization and dynamics of the active PEPRs remain largely unknown. We used live-cell imaging of the fluorescently labeled and bioactive pep1 to visualize the intracellular behavior of the PEPRs in the Arabidopsis root meristem. We found that AtPep1 decorated the plasma membrane (PM) in a receptor-dependent manner and cointernalized with PEPRs. Trafficking of the AtPep1-PEPR1 complexes to the vacuole required neither the trans-Golgi network/early endosome (TGN/EE)-localized vacuolar H+ -ATPase activity nor the function of the brefeldin A-sensitive ADP-ribosylation factor-guanine exchange factors (ARF-GEFs). In addition, AtPep1 and different TGN/EE markers colocalized only rarely, implying that the intracellular route of this receptor-ligand pair is largely independent of the TGN/EE. Inducible overexpression of the Arabidopsis clathrin coat disassembly factor, Auxilin2, which inhibits clathrin-mediated endocytosis (CME), impaired the AtPep1-PEPR1 internalization and compromised AtPep1-mediated responses. Our results show that clathrin function at the PM is required to induce plant defense responses, likely through CME of cell surface-located signaling components.

Nitrate controls root development through posttranscriptional regulation of the NRT1.1/NPF6.3 transporter sensor - Bouguyon, Eléonore; Perrine Walker, Francine; Pervent, Marjorie; Rochette, Juliette; Cuesta, Candela; Benková, Eva; Martinière, Alexandre; Bach, Lien; Krouk, Gabriel; Gojon, Alain; Nacry, Philippe (Plant Physiology)
Plants are able to modulate root growth and development to optimize their nitrogen nutrition. In Arabidopsis (Arabidopsis thaliana), the adaptive root response to nitrate (NO3 -) depends on the NRT1.1/NPF6.3 transporter/sensor. NRT1.1 represses emergence of lateral root primordia (LRPs) at low concentration or absence of NO3 - through its auxin transport activity that lowers auxin accumulation in LR. However, these functional data strongly contrast with the known transcriptional regulation of NRT1.1, which is markedly repressed in LRPs in the absence of NO3 -. To explain this discrepancy, we investigated in detail the spatiotemporal expression pattern of the NRT1.1 protein during LRP development and combined local transcript analysis with the use of transgenic lines expressing tagged NRT1.1 proteins. Our results show that although NO3 - stimulates NRT1.1 transcription and probably mRNA stability both in primary root tissues and in LRPs, it acts differentially on protein accumulation, depending on the tissues considered with stimulation in cortex and epidermis of the primary root and a strong repression in LRPs and to a lower extent at the primary root tip. This demonstrates that NRT1.1 is strongly regulated at the posttranscriptional level by tissue-specific mechanisms. These mechanisms are crucial for controlling the large palette of adaptive responses to NO3 - mediated by NRT1.1 as they ensure that the protein is present in the proper tissue under the specific conditions where it plays a signaling role in this particular tissue.

On eigenvalues of random complexes - Gundert, Anna; Wagner, Uli (Israel Journal of Mathematics)
We consider higher-dimensional generalizations of the normalized Laplacian and the adjacency matrix of graphs and study their eigenvalues for the Linial–Meshulam model Xk(n, p) of random k-dimensional simplicial complexes on n vertices. We show that for p = Ω(logn/n), the eigenvalues of each of the matrices are a.a.s. concentrated around two values. The main tool, which goes back to the work of Garland, are arguments that relate the eigenvalues of these matrices to those of graphs that arise as links of (k - 2)-dimensional faces. Garland’s result concerns the Laplacian; we develop an analogous result for the adjacency matrix. The same arguments apply to other models of random complexes which allow for dependencies between the choices of k-dimensional simplices. In the second part of the paper, we apply this to the question of possible higher-dimensional analogues of the discrete Cheeger inequality, which in the classical case of graphs relates the eigenvalues of a graph and its edge expansion. It is very natural to ask whether this generalizes to higher dimensions and, in particular, whether the eigenvalues of the higher-dimensional Laplacian capture the notion of coboundary expansion—a higher-dimensional generalization of edge expansion that arose in recent work of Linial and Meshulam and of Gromov; this question was raised, for instance, by Dotterrer and Kahle. We show that this most straightforward version of a higher-dimensional discrete Cheeger inequality fails, in quite a strong way: For every k ≥ 2 and n ∈ N, there is a k-dimensional complex Yn k on n vertices that has strong spectral expansion properties (all nontrivial eigenvalues of the normalised k-dimensional Laplacian lie in the interval [1−O(1/√1), 1+0(1/√1]) but whose coboundary expansion is bounded from above by O(log n/n) and so tends to zero as n → ∞; moreover, Yn k can be taken to have vanishing integer homology in dimension less than k.

Fixed energy universality for generalized wigner matrices - Bourgade, Paul; Erdös, László; Yau, Horngtzer; Yin, Jun (Communications on Pure and Applied Mathematics)
We prove the Wigner-Dyson-Mehta conjecture at fixed energy in the bulk of the spectrum for generalized symmetric and Hermitian Wigner matrices. Previous results concerning the universality of random matrices either require an averaging in the energy parameter or they hold only for Hermitian matrices if the energy parameter is fixed. We develop a homogenization theory of the Dyson Brownian motion and show that microscopic universality follows from mesoscopic statistics.

Callan-Jones et al. Reply - Callan Jones, Andrew; Ruprecht, Verena; Wieser, Stefan; Heisenberg, Carl-Philipp J; Voituriez, Raphaël (Physical Review Letters)

Seedlings’ strategy to overcome a soil barrier - Zhu, Qiang; Benková, Eva (Trends in Plant Science)
The impact of the plant hormone ethylene on seedling development has long been recognized; however, its ecophysiological relevance is unexplored. Three recent studies demonstrate that ethylene is a critical endogenous integrator of various environmental signals including mechanical stress, light, and oxygen availability during seedling germination and growth through the soil.

Rotation of cold molecular ions inside a Bose-Einstein condensate - Midya, Bikashkali; Tomza, Michał; Schmidt, Richard; Lemeshko, Mikhail (Physical Review A - Atomic, Molecular, and Optical Physics)
We use recently developed angulon theory [R. Schmidt and M. Lemeshko, Phys. Rev. Lett. 114, 203001 (2015)PRLTAO0031-900710.1103/PhysRevLett.114.203001] to study the rotational spectrum of a cyanide molecular anion immersed into Bose-Einstein condensates of rubidium and strontium. Based on ab initio potential energy surfaces, we provide a detailed study of the rotational Lamb shift and many-body-induced fine structure which arise due to dressing of molecular rotation by a field of phonon excitations. We demonstrate that the magnitude of these effects is large enough in order to be observed in modern experiments on cold molecular ions. Furthermore, we introduce a novel method to construct pseudopotentials starting from the ab initio potential energy surfaces, which provides a means to obtain effective coupling constants for low-energy polaron models.

Brassinosteroids participate in the control of basal and acquired freezing tolerance of plants - Eremina, Marina; Unterholzner, Simon; Rathnayake, Ajith; Castellanos, Marcos; Khan-Djamei, Mamoona; Kügler, Karl; May, Sean; Mayer, Klaus; Rozhon, Wilfried; Poppenberger, Brigitte (PNAS)
Brassinosteroids (BRs) are growth-promoting plant hormones that play a role in abiotic stress responses, but molecular modes that enable this activity remain largely unknown. Here we show that BRs participate in the regulation of freezing tolerance. BR signaling-defective mutants of Arabidopsis thaliana were hypersensitive to freezing before and after cold acclimation. The constitutive activation of BR signaling, in contrast, enhanced freezing resistance. Evidence is provided that the BR-controlled basic helix-loop-helix transcription factor CESTA (CES) can contribute to the constitutive expression of the C-REPEAT/DEHYDRATION-RESPONSIVE ELEMENT BINDING FACTOR (CBF) transcriptional regulators that control cold responsive (COR) gene expression. In addition, CBF-independent classes of BR-regulated COR genes are identified that are regulated in a BR- and CES-dependent manner during cold acclimation. A model is presented in which BRs govern different cold-responsive transcriptional cascades through the post-translational modification of CES and redundantly acting factors. This contributes to the basal resistance against freezing stress, but also to the further improvement of this resistance through cold acclimation.

Focal adhesion-independent cell migration - Paluch, Ewa; Aspalter, Irene; Sixt, Michael K (Annual Review of Cell and Developmental Biology)
Cell migration is central to a multitude of physiological processes, including embryonic development, immune surveillance, and wound healing, and deregulated migration is key to cancer dissemination. Decades of investigations have uncovered many of the molecular and physical mechanisms underlying cell migration. Together with protrusion extension and cell body retraction, adhesion to the substrate via specific focal adhesion points has long been considered an essential step in cell migration. Although this is true for cells moving on two-dimensional substrates, recent studies have demonstrated that focal adhesions are not required for cells moving in three dimensions, in which confinement is sufficient to maintain a cell in contact with its substrate. Here, we review the investigations that have led to challenging the requirement of specific adhesions for migration, discuss the physical mechanisms proposed for cell body translocation during focal adhesion-independent migration, and highlight the remaining open questions for the future.

Reversible FMN dissociation from Escherichia coli respiratory complex I - Holt, Peter; Efremov, Rouslan; Nakamaru Ogiso, Eiko; Sazanov, Leonid A (Biochimica et Biophysica Acta - Bioenergetics)
Respiratory complex I transfers electrons from NADH to quinone, utilizing the reaction energy to translocate protons across the membrane. It is a key enzyme of the respiratory chain of many prokaryotic and most eukaryotic organisms. The reversible NADH oxidation reaction is facilitated in complex I by non-covalently bound flavin mononucleotide (FMN). Here we report that the catalytic activity of E. coli complex I with artificial electron acceptors potassium ferricyanide (FeCy) and hexaamineruthenium (HAR) is significantly inhibited in the enzyme pre-reduced by NADH. Further, we demonstrate that the inhibition is caused by reversible dissociation of FMN. The binding constant (Kd) for FMN increases from the femto- or picomolar range in oxidized complex I to the nanomolar range in the NADH reduced enzyme, with an FMN dissociation time constant of ~ 5 s. The oxidation state of complex I, rather than that of FMN, proved critical to the dissociation. Such dissociation is not observed with the T. thermophilus enzyme and our analysis suggests that the difference may be due to the unusually high redox potential of Fe-S cluster N1a in E. coli. It is possible that the enzyme attenuates ROS production in vivo by releasing FMN under highly reducing conditions.

Periodic striped ground states in Ising models with competing interactions - Giuliani, Alessandro; Seiringer, Robert (Communications in Mathematical Physics)
We consider Ising models in two and three dimensions, with short range ferromagnetic and long range, power-law decaying, antiferromagnetic interactions. We let J be the ratio between the strength of the ferromagnetic to antiferromagnetic interactions. The competition between these two kinds of interactions induces the system to form domains of minus spins in a background of plus spins, or vice versa. If the decay exponent p of the long range interaction is larger than dÂ +Â 1, with d the space dimension, this happens for all values of J smaller than a critical value Jc(p), beyond which the ground state is homogeneous. In this paper, we give a characterization of the infinite volume ground states of the system, for pÂ >Â 2d and J in a left neighborhood of Jc(p). In particular, we prove that the quasi-one-dimensional states consisting of infinite stripes (dÂ =Â 2) or slabs (dÂ =Â 3), all of the same optimal width and orientation, and alternating magnetization, are infinite volume ground states. Our proof is based on localization bounds combined with reflection positivity.

Extremal positive semidefinite matrices whose sparsity pattern is given by graphs without K5 minors - Solus, Liam T; Uhler, Caroline; Yoshida, Ruriko (Linear Algebra and Its Applications)
For a graph G with p vertices the closed convex cone S⪰0(G) consists of all real positive semidefinite p×p matrices whose sparsity pattern is given by G, that is, those matrices with zeros in the off-diagonal entries corresponding to nonedges of G. The extremal rays of this cone and their associated ranks have applications to matrix completion problems, maximum likelihood estimation in Gaussian graphical models in statistics, and Gauss elimination for sparse matrices. While the maximum rank of an extremal ray in S⪰0(G), known as the sparsity order of G, has been characterized for different classes of graphs, we here study all possible extremal ranks of S⪰0(G). We investigate when the geometry of the (±1)-cut polytope of G yields a polyhedral characterization of the set of extremal ranks of S⪰0(G). For a graph G without K5 minors, we show that appropriately chosen normal vectors to the facets of the (±1)-cut polytope of G specify the off-diagonal entries of extremal matrices in S⪰0(G). We also prove that for appropriately chosen scalars the constant term of the linear equation of each facet-supporting hyperplane is the rank of its corresponding extremal matrix in S⪰0(G). Furthermore, we show that if G is series-parallel then this gives a complete characterization of all possible extremal ranks of S⪰0(G). Consequently, the sparsity order problem for series-parallel graphs can be solved in terms of polyhedral geometry.

Compounds that select against the tetracycline-resistance efflux pump - Stone, Laura; Baym, Michael; Lieberman, Tami; Chait, Remy P; Clardy, Jon; Kishony, Roy (Nature Chemical Biology)
We developed a competition-based screening strategy to identify compounds that invert the selective advantage of antibiotic resistance. Using our assay, we screened over 19,000 compounds for the ability to select against the TetA tetracycline-resistance efflux pump in Escherichia coli and identified two hits, β-thujaplicin and disulfiram. Treating a tetracycline-resistant population with β-thujaplicin selects for loss of the resistance gene, enabling an effective second-phase treatment with doxycycline.

Multiple covers with balls II: Weighted averages - Edelsbrunner, Herbert; Iglesias Ham, Mabel (Electronic Notes in Discrete Mathematics)
Voronoi diagrams and Delaunay triangulations have been extensively used to represent and compute geometric features of point configurations. We introduce a generalization to poset diagrams and poset complexes, which contain order-k and degree-k Voronoi diagrams and their duals as special cases. Extending a result of Aurenhammer from 1990, we show how to construct poset diagrams as weighted Voronoi diagrams of average balls.

Computing the Thurston–Bennequin invariant in open books - Durst, Sebastian; Kegel, Marc; Klukas, Mirko D (Acta Mathematica Hungarica)
We give explicit formulas and algorithms for the computation of the Thurston–Bennequin invariant of a nullhomologous Legendrian knot on a page of a contact open book and on Heegaard surfaces in convex position. Furthermore, we extend the results to rationally nullhomologous knots in arbitrary 3-manifolds.

A neuronal circuit for colour vision based on rod-cone opponency - Maximilian Jösch; Meister, Markus (Nature)
In bright light, cone-photoreceptors are active and colour vision derives from a comparison of signals in cones with different visual pigments. This comparison begins in the retina, where certain retinal ganglion cells have 'colour-opponent' visual responses-excited by light of one colour and suppressed by another colour. In dim light, rod-photoreceptors are active, but colour vision is impossible because they all use the same visual pigment. Instead, the rod signals are thought to splice into retinal circuits at various points, in synergy with the cone signals. Here we report a new circuit for colour vision that challenges these expectations. A genetically identified type of mouse retinal ganglion cell called JAMB (J-RGC), was found to have colour-opponent responses, OFF to ultraviolet (UV) light and ON to green light. Although the mouse retina contains a green-sensitive cone, the ON response instead originates in rods. Rods and cones both contribute to the response over several decades of light intensity. Remarkably, the rod signal in this circuit is antagonistic to that from cones. For rodents, this UV-green channel may play a role in social communication, as suggested by spectral measurements from the environment. In the human retina, all of the components for this circuit exist as well, and its function can explain certain experiences of colour in dim lights, such as a 'blue shift' in twilight. The discovery of this genetically defined pathway will enable new targeted studies of colour processing in the brain.

Reconstruction of genetically identified neurons imaged by serial-section electron microscopy - Maximilian Jösch; Mankus, David; Yamagata, Masahito; Shahbazi, Ali; Schalek, Richard L; Suissa-Peleg, Adi; Meister, Markus; Lichtman, Jeff W; Scheirer, Walter J; Sanes, Joshua R (eLife)
Resolving patterns of synaptic connectivity in neural circuits currently requires serial section electron microscopy. However, complete circuit reconstruction is prohibitively slow and may not be necessary for many purposes such as comparing neuronal structure and connectivity among multiple animals. Here, we present an alternative strategy, targeted reconstruction of specific neuronal types. We used viral vectors to deliver peroxidase derivatives, which catalyze production of an electron-dense tracer, to genetically identify neurons, and developed a protocol that enhances the electron-density of the labeled cells while retaining the quality of the ultrastructure. The high contrast of the marked neurons enabled two innovations that speed data acquisition: targeted high-resolution reimaging of regions selected from rapidly-acquired lower resolution reconstruction, and an unsupervised segmentation algorithm. This pipeline reduces imaging and reconstruction times by two orders of magnitude, facilitating directed inquiry of circuit motifs.

DefSense: computational design of customized deformable input devices - Bächer, Moritz; Hepp, Benjamin; Pece, Fabrizio; Kry, Paul; Bickel, Bernd; Thomaszewski, Bernhard; Hilliges, Otmar
We present a novel optimization-based algorithm for the design and fabrication of customized, deformable input devices, capable of continuously sensing their deformation. We propose to embed piezoresistive sensing elements into flexible 3D printed objects. These sensing elements are then utilized to recover rich and natural user interactions at runtime. Designing such objects is a challenging and hard problem if attempted manually for all but the simplest geometries and deformations. Our method simultaneously optimizes the internal routing of the sensing elements and computes a mapping from low-level sensor readings to user-specified outputs in order to minimize reconstruction error. We demonstrate the power and flexibility of the approach by designing and fabricating a set of flexible input devices. Our results indicate that the optimization-based design greatly outperforms manual routings in terms of reconstruction accuracy and thus interaction fidelity.

A higher-order large scale regularity theory for random elliptic operators - Julian Fischer; Otto, Felix (Communications in Partial Differential Equations)
We develop a large-scale regularity theory of higher order for divergence-form elliptic equations with heterogeneous coefficient fields a in the context of stochastic homogenization. The large-scale regularity of a-harmonic functions is encoded by Liouville principles: The space of a-harmonic functions that grow at most like a polynomial of degree k has the same dimension as in the constant-coefficient case. This result can be seen as the qualitative side of a large-scale Ck,α-regularity theory, which in the present work is developed in the form of a corresponding Ck,α-“excess decay” estimate: For a given a-harmonic function u on a ball BR, its energy distance on some ball Br to the above space of a-harmonic functions that grow at most like a polynomial of degree k has the natural decay in the radius r above some minimal radius r0. Though motivated by stochastic homogenization, the contribution of this paper is of purely deterministic nature: We work under the assumption that for the given realization a of the coefficient field, the couple (φ, σ) of scalar and vector potentials of the harmonic coordinates, where φ is the usual corrector, grows sublinearly in a mildly quantified way. We then construct “kth-order correctors” and thereby the space of a-harmonic functions that grow at most like a polynomial of degree k, establish the above excess decay, and then the corresponding Liouville principle.

Behaviour of free boundaries in thin-film flow: The regime of strong slippage and the regime of very weak slippage - Julian Fischer (Annales de l'Institut Henri Poincare (C) Non Linear Analysis)
We analyze the behaviour of free boundaries in thin-film flow in the regime of strong slippage n∈[1,2) and in the regime of very weak slippage n∈,3) qualitatively and quantitatively. In the regime of strong slippage, we construct initial data which are bounded from above by the steady state but for which nevertheless instantaneous forward motion of the free boundary occurs. This shows that the initial behaviour of the free boundary is not determined just by the growth of the initial data at the free boundary. Note that this is a new phenomenon for degenerate parabolic equations which is specific for higher-order equations. Furthermore, this result resolves a controversy in the literature over optimality of sufficient conditions for the occurrence of a waiting time phenomenon. In contrast, in the regime of very weak slippage we derive lower bounds on free boundary propagation which are optimal in the sense that they coincide up to a constant factor with the known upper bounds. In particular, in this regime the growth of the initial data at the free boundary fully determines the initial behaviour of the interface.

Analysis of a modified second-order mixed hybrid BDM1 finite element method for transport problems in divergence form - Brunner, Fabian; Julian Fischer; Knabner, Peter (SIAM Journal on Numerical Analysis)
We prove optimal second order convergence of a modified lowest-order Brezzi-Douglas-Marini (BDM1) mixed finite element scheme for advection-diffusion problems in divergence form. If advection is present, it is known that the total flux is approximated only with first-order accuracy by the classical BDM1 mixed method, which is suboptimal since the same order of convergence is obtained if the computationally less expensive Raviart-Thomas (RT0) element is used. The modification that was first proposed by Brunner et al. [Adv. Water Res., 35 (2012),pp. 163-171] is based on the hybrid problem formulation and consists in using the Lagrange multipliers for the discretization of the advective term instead of the cellwise constant approximation of the scalar unknown.

Plasticity-dependent, full detonation at hippocampal mossy fiber–CA3 pyramidal neuron synapses - Vyleta, Nicholas; Borges Merjane, Carolina; Jonas, Peter M (eLife)
Mossy fiber synapses on CA3 pyramidal cells are 'conditional detonators' that reliably discharge postsynaptic targets. The 'conditional' nature implies that burst activity in dentate gyrus granule cells is required for detonation. Whether single unitary excitatory postsynaptic potentials (EPSPs) trigger spikes in CA3 neurons remains unknown. Mossy fiber synapses exhibit both pronounced short-term facilitation and uniquely large post-tetanic potentiation (PTP). We tested whether PTP could convert mossy fiber synapses from subdetonator into detonator mode, using a recently developed method to selectively and noninvasively stimulate individual presynaptic terminals in rat brain slices. Unitary EPSPs failed to initiate a spike in CA3 neurons under control conditions, but reliably discharged them after induction of presynaptic short-term plasticity. Remarkably, PTP switched mossy fiber synapses into full detonators for tens of seconds. Plasticity-dependent detonation may be critical for efficient coding, storage, and recall of information in the granule cell–CA3 cell network.

Stability in graphs and games - Brázdil, Tomáš; Forejt, Vojtěch; Kučera, Antonín; Novotny, Petr
We study graphs and two-player games in which rewards are assigned to states, and the goal of the players is to satisfy or dissatisfy certain property of the generated outcome, given as a mean payoff property. Since the notion of mean-payoff does not reflect possible fluctuations from the mean-payoff along a run, we propose definitions and algorithms for capturing the stability of the system, and give algorithms for deciding if a given mean payoff and stability objective can be ensured in the system.

Scale-invariant systems realize nonlinear differential operators - Lang, Moritz; Sontag, Eduardo
In recent years, several biomolecular systems have been shown to be scale-invariant (SI), i.e. to show the same output dynamics when exposed to geometrically scaled input signals (u → pu, p > 0) after pre-adaptation to accordingly scaled constant inputs. In this article, we show that SI systems-as well as systems invariant with respect to other input transformations-can realize nonlinear differential operators: when excited by inputs obeying functional forms characteristic for a given class of invariant systems, the systems' outputs converge to constant values directly quantifying the speed of the input.

Indefinite-horizon reachability in Goal-DEC-POMDPs - Chatterjee, Krishnendu; Chmelik, Martin (Proceedings of the Twenty-Sixth International Conference on International Conference on Automated Planning and Scheduling)
DEC-POMDPs extend POMDPs to a multi-agent setting, where several agents operate in an uncertain environment independently to achieve a joint objective. DEC-POMDPs have been studied with finite-horizon and infinite-horizon discounted-sum objectives, and there exist solvers both for exact and approximate solutions. In this work we consider Goal-DEC-POMDPs, where given a set of target states, the objective is to ensure that the target set is reached with minimal cost. We consider the indefinite-horizon (infinite-horizon with either discounted-sum, or undiscounted-sum, where absorbing goal states have zero-cost) problem. We present a new and novel method to solve the problem that extends methods for finite-horizon DEC-POMDPs and the RTDP-Bel approach for POMDPs. We present experimental results on several examples, and show that our approach presents promising results. Copyright

De novo transcriptome assembly and sex-biased gene expression in the cyclical parthenogenetic Daphnia galeata - Huylmans, Ann K; López Ezquerra, Alberto; Parsch, John; Cordellier, Mathilde (Genome Biology and Evolution)
Daphnia species have become models for ecological genomics and exhibit interesting features, such as high phenotypic plasticity and a densely packed genome with many lineage-specific genes. They are also cyclic parthenogenetic, with alternating asexual and sexual cycles and environmental sex determination. Here, we present a de novo transcriptome assembly of over 32,000 D. galeata genes and use it to investigate gene expression in females and spontaneously produced males of two clonal lines derived from lakes in Germany and the Czech Republic. We find that only a low percentage (18%) of genes shows sex-biased expression and that there are many more female-biased gene (FBG) than male-biased gene (MBG). Furthermore, FBGs tend to be more conserved between species than MBGs in both sequence and expression. These patterns may be a consequence of cyclic parthenogenesis leading to a relaxation of purifying selection on MBGs. The two clonal lines show considerable differences in both number and identity of sex-biased genes, suggesting that they may have reproductive strategies differing in their investment in sexual reproduction. Orthologs of key genes in the sex determination and juvenile hormone pathways, which are thought to be important for the transition from asexual to sexual reproduction, are present in D. galeata and highly conserved among Daphnia species.

Stochastic shortest path with energy constraints in POMDPs - Brázdil, Tomáš; Chatterjee, Krishnendu; Chmelik, Martin; Gupta, Anchit; Novotny, Petr (Proceedings of the 15th International Conference on Autonomous Agents and Multiagent Systems)
We consider partially observable Markov decision processes (POMDPs) with a set of target states and positive integer costs associated with every transition. The traditional optimization objective (stochastic shortest path) asks to minimize the expected total cost until the target set is reached. We extend the traditional framework of POMDPs to model energy consumption, which represents a hard constraint. The energy levels may increase and decrease with transitions, and the hard constraint requires that the energy level must remain positive in all steps till the target is reached. First, we present a novel algorithm for solving POMDPs with energy levels, developing on existing POMDP solvers and using RTDP as its main method. Our second contribution is related to policy representation. For larger POMDP instances the policies computed by existing solvers are too large to be understandable. We present an automated procedure based on machine learning techniques that automatically extracts important decisions of the policy allowing us to compute succinct human readable policies. Finally, we show experimentally that our algorithm performs well and computes succinct policies on a number of POMDP instances from the literature that were naturally enhanced with energy levels.

Optimizing the expected mean payoff in Energy Markov Decision Processes - Brázdil, Tomáš; Kučera, Antonín; Novotny, Petr
Energy Markov Decision Processes (EMDPs) are finite-state Markov decision processes where each transition is assigned an integer counter update and a rational payoff. An EMDP configuration is a pair s(n), where s is a control state and n is the current counter value. The configurations are changed by performing transitions in the standard way. We consider the problem of computing a safe strategy (i.e., a strategy that keeps the counter non-negative) which maximizes the expected mean payoff.

Billiards in convex bodies with acute angles - Akopyan, Arseniy; Balitskiy, Alexey (Israel Journal of Mathematics)
In this paper we investigate the existence of closed billiard trajectories in not necessarily smooth convex bodies. In particular, we show that if a body K ⊂ Rd has the property that the tangent cone of every non-smooth point q ∉ ∂K is acute (in a certain sense), then there is a closed billiard trajectory in K.

Activity dependent plasticity of hippocampal place maps - Schönenberger, Philipp; O'Neill, Joseph; Csicsvari, Jozsef L (Nature Communications)
Hippocampal neurons encode a cognitive map of space. These maps are thought to be updated during learning and in response to changes in the environment through activity-dependent synaptic plasticity. Here we examine how changes in activity influence spatial coding in rats using halorhodopsin-mediated, spatially selective optogenetic silencing. Halorhoposin stimulation leads to light-induced suppression in many place cells and interneurons; some place cells increase their firing through disinhibition, whereas some show no effect. We find that place fields of the unaffected subpopulation remain stable. On the other hand, place fields of suppressed place cells were unstable, showing remapping across sessions before and after optogenetic inhibition. Disinhibited place cells had stable maps but sustained an elevated firing rate. These findings suggest that place representation in the hippocampus is constantly governed by activity-dependent processes, and that disinhibition may provide a mechanism for rate remapping.

Cytokinin response factor 6 represses cytokinin-associated genes during oxidative stress - Zwack, Paul; De Clercq, Inge; Howton, Timothy; Hallmark, H Tucker; Hurny, Andrej; Keshishian, Erika; Parish, Alyssa; Benková, Eva; Mukhtar, M Shahid; Van Breusegem, Frank; Rashotte, Aaron (Plant Physiology)
Cytokinin is a phytohormone that is well known for its roles in numerous plant growth and developmental processes, yet it has also been linked to abiotic stress response in a less defined manner. Arabidopsis (Arabidopsis thaliana) Cytokinin Response Factor 6 (CRF6) is a cytokinin-responsive AP2/ERF-family transcription factor that, through the cytokinin signaling pathway, plays a key role in the inhibition of dark-induced senescence. CRF6 expression is also induced by oxidative stress, and here we show a novel function for CRF6 in relation to oxidative stress and identify downstream transcriptional targets of CRF6 that are repressed in response to oxidative stress. Analysis of transcriptomic changes in wild-type and crf6 mutant plants treated with H2O2 identified CRF6-dependent differentially expressed transcripts, many of which were repressed rather than induced. Moreover, many repressed genes also show decreased expression in 35S:CRF6 overexpressing plants. Together, these findings suggest that CRF6 functions largely as a transcriptional repressor. Interestingly, among the H2O2 repressed CRF6-dependent transcripts was a set of five genes associated with cytokinin processes: (signaling) ARR6, ARR9, ARR11, (biosynthesis) LOG7, and (transport) ABCG14. We have examined mutants of these cytokinin-associated target genes to reveal novel connections to oxidative stress. Further examination of CRF6-DNA interactions indicated that CRF6 may regulate its targets both directly and indirectly. Together, this shows that CRF6 functions during oxidative stress as a negative regulator to control this cytokinin-associated module of CRF6- dependent genes and establishes a novel connection between cytokinin and oxidative stress response.

Humans choose representatives who enforce cooperation in social dilemmas through extortion - Milinski, Manfred; Hilbe, Christian; Semmann, Dirk; Sommerfeld, Ralf; Marotzke, Jochem (Nature Communications)
Social dilemmas force players to balance between personal and collective gain. In many dilemmas, such as elected governments negotiating climate-change mitigation measures, the decisions are made not by individual players but by their representatives. However, the behaviour of representatives in social dilemmas has not been investigated experimentally. Here inspired by the negotiations for greenhouse-gas emissions reductions, we experimentally study a collective-risk social dilemma that involves representatives deciding on behalf of their fellow group members. Representatives can be re-elected or voted out after each consecutive collective-risk game. Selfish players are preferentially elected and are hence found most frequently in the "representatives" treatment. Across all treatments, we identify the selfish players as extortioners. As predicted by our mathematical model, their steadfast strategies enforce cooperation from fair players who finally compensate almost completely the deficit caused by the extortionate co-players. Everybody gains, but the extortionate representatives and their groups gain the most.

Pervasive selection for and against antibiotic resistance in inhomogeneous multistress environments - Chait, Remy P; Palmer, Adam; Yelin, Idan; Kishony, Roy (Nature Communications)
Antibiotic-sensitive and -resistant bacteria coexist in natural environments with low, if detectable, antibiotic concentrations. Except possibly around localized antibiotic sources, where resistance can provide a strong advantage, bacterial fitness is dominated by stresses unaffected by resistance to the antibiotic. How do such mixed and heterogeneous conditions influence the selective advantage or disadvantage of antibiotic resistance? Here we find that sub-inhibitory levels of tetracyclines potentiate selection for or against tetracycline resistance around localized sources of almost any toxin or stress. Furthermore, certain stresses generate alternating rings of selection for and against resistance around a localized source of the antibiotic. In these conditions, localized antibiotic sources, even at high strengths, can actually produce a net selection against resistance to the antibiotic. Our results show that interactions between the effects of an antibiotic and other stresses in inhomogeneous environments can generate pervasive, complex patterns of selection both for and against antibiotic resistance.

Quantitative monitor automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan
In this paper we review various automata-theoretic formalisms for expressing quantitative properties. We start with finite-state Boolean automata that express the traditional regular properties. We then consider weighted ω-automata that can measure the average density of events, which finite-state Boolean automata cannot. However, even weighted ω-automata cannot express basic performance properties like average response time. We finally consider two formalisms of weighted ω-automata with monitors, where the monitors are either (a) counters or (b) weighted automata themselves. We present a translation result to establish that these two formalisms are equivalent. Weighted ω-automata with monitors generalize weighted ω-automata, and can express average response time property. They present a natural, robust, and expressive framework for quantitative specifications, with important decidable properties.

TIR1 AFB Aux IAA auxin perception mediates rapid cell wall acidification and growth of Arabidopsis hypocotyls - Fendrych, Matyas; Leung, Jeffrey; Friml, Jirí (eLife)
Despite being composed of immobile cells, plants reorient along directional stimuli. The hormone auxin is redistributed in stimulated organs leading to differential growth and bending. Auxin application triggers rapid cell wall acidification and elongation of aerial organs of plants, but the molecular players mediating these effects are still controversial. Here we use genetically-encoded pH and auxin signaling sensors, pharmacological and genetic manipulations available for Arabidopsis etiolated hypocotyls to clarify how auxin is perceived and the downstream growth executed. We show that auxin-induced acidification occurs by local activation of H+-ATPases, which in the context of gravity response is restricted to the lower organ side. This auxin-stimulated acidification and growth require TIR1/AFB-Aux/IAA nuclear auxin perception. In addition, auxin-induced gene transcription and specifically SAUR proteins are crucial downstream mediators of this growth. Our study provides strong experimental support for the acid growth theory and clarified the contribution of the upstream auxin perception mechanisms.

Dissipative preparation of antiferromagnetic order in the Fermi-Hubbard model - Kaczmarczyk, Jan; Weimer, Hendrik; Lemeshko, Mikhail (New Journal of Physics)
The Fermi-Hubbard model is one of the key models of condensed matter physics, which holds a potential for explaining the mystery of high-temperature superconductivity. Recent progress in ultracold atoms in optical lattices has paved the way to studying the model’s phase diagram using the tools of quantum simulation, which emerged as a promising alternative to the numerical calculations plagued by the infamous sign problem. However, the temperatures achieved using elaborate laser cooling protocols so far have been too high to show the appearance of antiferromagnetic (AF) and superconducting quantum phases directly. In this work, we demonstrate that using the machinery of dissipative quantum state engineering, one can observe the emergence of the AF order in the Fermi-Hubbard model with fermions in optical lattices. The core of the approach is to add incoherent laser scattering in such a way that the AF state emerges as the dark state of the driven-dissipative dynamics. The proposed controlled dissipation channels described in this work are straightforward to add to already existing experimental setups.

The big match in small space - Hansen, Kristoffer; Ibsen-Jensen, Rasmus; Koucký, Michal
We study repeated games with absorbing states, a type of two-player, zero-sum concurrent mean-payoff games with the prototypical example being the Big Match of Gillete (1957). These games may not allow optimal strategies but they always have ε-optimal strategies. In this paper we design ε-optimal strategies for Player 1 in these games that use only O(log log T) space. Furthermore, we construct strategies for Player 1 that use space s(T), for an arbitrary small unbounded non-decreasing function s, and which guarantee an ε-optimal value for Player 1 in the limit superior sense. The previously known strategies use space Ω(log T) and it was known that no strategy can use constant space if it is ε-optimal even in the limit superior sense. We also give a complementary lower bound. Furthermore, we also show that no Markov strategy, even extended with finite memory, can ensure value greater than 0 in the Big Match, answering a question posed by Neyman [11].

Plasma membrane: Negative attraction - Molnar, Gergely; Fendrych, Matyas; Friml, Jirí (Nature Plants)
The electrostatic charge at the inner surface of the plasma membrane is strongly negative in higher organisms. A new study shows that phosphatidylinositol-4-phosphate plays a critical role in establishing plasma membrane surface charge in Arabidopsis, which regulates the correct localization of signalling components.

Spatiotemporal microbial evolution on antibiotic landscapes - Baym, Michael; Lieberman, Tami; Kelsic, Eric; Chait, Remy P; Gross, Rotem; Yelin, Idan; Kishony, Roy (Science)
A key aspect of bacterial survival is the ability to evolve while migrating across spatially varying environmental challenges. Laboratory experiments, however, often study evolution in well-mixed systems. Here, we introduce an experimental device, the microbial evolution and growth arena (MEGA)-plate, in which bacteria spread and evolved on a large antibiotic landscape (120 × 60 centimeters) that allowed visual observation of mutation and selection in a migrating bacterial front.While resistance increased consistently, multiple coexisting lineages diversified both phenotypically and genotypically. Analyzing mutants at and behind the propagating front,we found that evolution is not always led by the most resistant mutants; highly resistant mutants may be trapped behindmore sensitive lineages.TheMEGA-plate provides a versatile platformfor studying microbial adaption and directly visualizing evolutionary dynamics.

Tunable mechanical coupling between driven microelectromechanical resonators - Verbiest, Gerard; Xu, Duo; Goldsche, Matthias; Khodkov, Timofiy; Barzanjeh, Shabir; Von Den Driesch, Nils; Buca, Dan; Stampfer, Christoph (Applied Physics Letter)
We present a microelectromechanical system, in which a silicon beam is attached to a comb-drive actuator, which is used to tune the tension in the silicon beam and thus its resonance frequency. By measuring the resonance frequencies of the system, we show that the comb-drive actuator and the silicon beam behave as two strongly coupled resonators. Interestingly, the effective coupling rate (1.5 MHz) is tunable with the comb-drive actuator (10%) as well as with a side-gate (10%) placed close to the silicon beam. In contrast, the effective spring constant of the system is insensitive to either of them and changes only by 60.5%. Finally, we show that the comb-drive actuator can be used to switch between different coupling rates with a frequency of at least 10 kHz.

When non-elitism outperforms elitism for crossing fitness valleys - Oliveto, Pietro; Paixao, Tiago; Heredia, Jorge; Sudholt, Dirk; Trubenova, Barbora (Proceedings of the Genetic and Evolutionary Computation Conference 2016)
Crossing fitness valleys is one of the major obstacles to function optimization. In this paper we investigate how the structure of the fitness valley, namely its depth d and length ℓ, influence the runtime of different strategies for crossing these valleys. We present a runtime comparison between the (1+1) EA and two non-elitist nature-inspired algorithms, Strong Selection Weak Mutation (SSWM) and the Metropolis algorithm. While the (1+1) EA has to jump across the valley to a point of higher fitness because it does not accept decreasing moves, the non-elitist algorithms may cross the valley by accepting worsening moves. We show that while the runtime of the (1+1) EA algorithm depends critically on the length of the valley, the runtimes of the non-elitist algorithms depend crucially only on the depth of the valley. In particular, the expected runtime of both SSWM and Metropolis is polynomial in ℓ and exponential in d while the (1+1) EA is efficient only for valleys of small length. Moreover, we show that both SSWM and Metropolis can also efficiently optimize a rugged function consisting of consecutive valleys.

Synaptic mechanisms of pattern completion in the hippocampal CA3 network - Guzmán, José; Schlögl, Alois; Frotscher, Michael; Jonas, Peter M (Science)
The hippocampal CA3 region plays a key role in learning and memory. Recurrent CA3–CA3 synapses are thought to be the subcellular substrate of pattern completion. However, the synaptic mechanisms of this network computation remain enigmatic. To investigate these mechanisms, we combined functional connectivity analysis with network modeling. Simultaneous recording fromup to eight CA3 pyramidal neurons revealed that connectivity was sparse, spatially uniform, and highly enriched in disynaptic motifs (reciprocal, convergence,divergence, and chain motifs). Unitary connections were composed of one or two synaptic contacts, suggesting efficient use of postsynaptic space. Real-size modeling indicated that CA3 networks with sparse connectivity, disynaptic motifs, and single-contact connections robustly generated pattern completion.Thus, macro- and microconnectivity contribute to efficient memory storage and retrieval in hippocampal networks.

Deformation of a quantum many-particle system by a rotating impurity - Schmidt, Richard; Lemeshko, Mikhail (Physical Review X)
During the past 70 years, the quantum theory of angular momentum has been successfully applied to describing the properties of nuclei, atoms, and molecules, and their interactions with each other as well as with external fields. Because of the properties of quantum rotations, the angular-momentum algebra can be of tremendous complexity even for a few interacting particles, such as valence electrons of an atom, not to mention larger many-particle systems. In this work, we study an example of the latter: A rotating quantum impurity coupled to a many-body bosonic bath. In the regime of strong impurity-bath couplings, the problem involves the addition of an infinite number of angular momenta, which renders it intractable using currently available techniques. Here, we introduce a novel canonical transformation that allows us to eliminate the complex angular-momentum algebra from such a class of many-body problems. In addition, the transformation exposes the problem's constants of motion, and renders it solvable exactly in the limit of a slowly rotating impurity. We exemplify the technique by showing that there exists a critical rotational speed at which the impurity suddenly acquires one quantum of angular momentum from the many-particle bath. Such an instability is accompanied by the deformation of the phonon density in the frame rotating along with the impurity.

Bounded embeddings of graphs in the plane - Fulek, Radoslav
A drawing in the plane (ℝ2) of a graph G = (V,E) equipped with a function γ : V → ℕ is x-bounded if (i) x(u) < x(v) whenever γ(u) < γ(v) and (ii) γ(u) ≤ γ(w) ≤ γ(v), where uv ∈ E and γ(u) ≤ γ(v), whenever x(w) ∈ x(uv), where x(.) denotes the projection to the xaxis.We prove a characterization of isotopy classes of embeddings of connected graphs equipped with γ in the plane containing an x-bounded embedding.Then we present an efficient algorithm, which relies on our result, for testing the existence of an x-bounded embedding if the given graph is a forest.This partially answers a question raised recently by Angelini et al.and Chang et al., and proves that c-planarity testing of flat clustered graphs with three clusters is tractable when the underlying abstract graph is a forest.

Quantum electromechanics on silicon nitride nanomembranes - Fink, Johannes M; Kalaee, Mahmoud; Pitanti, Alessandro; Norte, Richard; Heinzle, Lukas; Davanço, Marcelo; Srinivasan, Kartik; Painter, Oskar (Nature Communications)
Radiation pressure has recently been used to effectively couple the quantum motion of mechanical elements to the fields of optical or microwave light. Integration of all three degrees of freedom—mechanical, optical and microwave—would enable a quantum interconnect between microwave and optical quantum systems. We present a platform based on silicon nitride nanomembranes for integrating superconducting microwave circuits with planar acoustic and optical devices such as phononic and photonic crystals. Using planar capacitors with vacuum gaps of 60 nm and spiral inductor coils of micron pitch we realize microwave resonant circuits with large electromechanical coupling to planar acoustic structures of nanoscale dimensions and femtoFarad motional capacitance. Using this enhanced coupling, we demonstrate microwave backaction cooling of the 4.48 MHz mechanical resonance of a nanobeam to an occupancy as low as 0.32. These results indicate the viability of silicon nitride nanomembranes as an all-in-one substrate for quantum electro-opto-mechanical experiments.

The effect of gene interactions on the long-term response to selection - Paixao, Tiago; Barton, Nicholas H (PNAS)
The role of gene interactions in the evolutionary process has long been controversial. Although some argue that they are not of importance, because most variation is additive, others claim that their effect in the long term can be substantial. Here, we focus on the long-term effects of genetic interactions under directional selection assuming no mutation or dominance, and that epistasis is symmetrical overall. We ask by how much the mean of a complex trait can be increased by selection and analyze two extreme regimes, in which either drift or selection dominate the dynamics of allele frequencies. In both scenarios, epistatic interactions affect the long-term response to selection by modulating the additive genetic variance. When drift dominates, we extend Robertson ’ s [Robertson A (1960) Proc R Soc Lond B Biol Sci 153(951):234 − 249] argument to show that, for any form of epistasis, the total response of a haploid population is proportional to the initial total genotypic variance. In contrast, the total response of a diploid population is increased by epistasis, for a given initial genotypic variance. When selection dominates, we show that the total selection response can only be increased by epistasis when s ome initially deleterious alleles become favored as the genetic background changes. We find a sim- ple approximation for this effect and show that, in this regime, it is the structure of the genotype - phenotype map that matters and not the variance components of the population.

Coexistence of nematic order and superconductivity in the Hubbard model - Kaczmarczyk, Jan; Schickling, Tobias; Bünemann, Jörg (Physical Review B - Condensed Matter and Materials Physics)
We study the interplay of nematic and superconducting order in the two-dimensional Hubbard model and show that they can coexist, especially when superconductivity is not the energetically dominant phase. Due to a breaking of the C4 symmetry, the coexisting phase inherently contains admixture of the s-wave pairing components. As a result, the superconducting gap exhibits nonstandard features including changed nodal directions. Our results also show that in the optimally doped regime the pure superconducting phase is typically unstable towards developing nematicity (breaking of the C4 symmetry). This has implications for the cuprate high-Tc superconductors, for which in this regime the so-called intertwined orders have recently been observed. Namely, the coexisting phase may be viewed as a precursor to such more involved patterns of symmetry breaking.

Superconducting cavity electromechanics on a silicon-on-insulator platform - Dieterle, Paul; Kalaee, Mahmoud; Fink, Johannes M; Painter, Oskar (Physical Review Applied)
Fabrication processes involving anhydrous hydrofluoric vapor etching are developed to create high-Q aluminum superconducting microwave resonators on free-standing silicon membranes formed from a silicon-on-insulator wafer. Using this fabrication process, a high-impedance 8.9-GHz coil resonator is coupled capacitively with a large participation ratio to a 9.7-MHz micromechanical resonator. Two-tone microwave spectroscopy and radiation pressure backaction are used to characterize the coupled system in a dilution refrigerator down to temperatures of Tf=11  mK, yielding a measured electromechanical vacuum coupling rate of g0/2π=24.6  Hz and a mechanical resonator Q factor of Qm=1.7×107. Microwave backaction cooling of the mechanical resonator is also studied, with a minimum phonon occupancy of nm≈16 phonons being realized at an elevated fridge temperature of Tf=211  mK.

Sewall Wright on evolution in Mendelian populations and the “Shifting Balance” - Barton, Nicholas H (Genetics)

Richard Hudson and Norman Kaplan on the coalescent process - Barton, Nicholas H (Genetics)

Deciding absorption - Barto, Libor; Kazda, Alexandr (International Journal of Algebra and Computation)
We characterize absorption in finite idempotent algebras by means of Jónsson absorption and cube term blockers. As an application we show that it is decidable whether a given subset is an absorbing subuniverse of an algebra given by the tables of its basic operations.

Generalized non-reflecting boundaries for fluid re-simulation - Bojsen-Hansen, Morten; Wojtan, Christopher J
When aiming to seamlessly integrate a fluid simulation into a larger scenario (like an open ocean), careful attention must be paid to boundary conditions. In particular, one must implement special "non-reflecting" boundary conditions, which dissipate out-going waves as they exit the simulation. Unfortunately, the state of the art in non-reflecting boundary conditions (perfectly-matched layers, or PMLs) only permits trivially simple inflow/outflow conditions, so there is no reliable way to integrate a fluid simulation into a more complicated environment like a stormy ocean or a turbulent river. This paper introduces the first method for combining nonreflecting boundary conditions based on PMLs with inflow/outflow boundary conditions that vary arbitrarily throughout space and time. Our algorithm is a generalization of stateof- the-art mean-flow boundary conditions in the computational fluid dynamics literature, and it allows for seamless integration of a fluid simulation into much more complicated environments. Our method also opens the door for previously-unseen postprocess effects like retroactively changing the location of solid obstacles, and locally increasing the visual detail of a pre-existing simulation.

Computational design of stable planar-rod structures - Miguel Villalba, Eder; Lepoutre, Mathias; Bickel, Bernd
We present a computational method for designing wire sculptures consisting of interlocking wires. Our method allows the computation of aesthetically pleasing structures that are structurally stable, efficiently fabricatable with a 2D wire bending machine, and assemblable without the need of additional connectors. Starting from a set of planar contours provided by the user, our method automatically tests for the feasibility of a design, determines a discrete ordering of wires at intersection points, and optimizes for the rest shape of the individual wires to maximize structural stability under frictional contact. In addition to their application to art, wire sculptures present an extremely efficient and fast alternative for low-fidelity rapid prototyping because manufacturing time and required material linearly scales with the physical size of objects. We demonstrate the effectiveness of our approach on a varied set of examples, all of which we fabricated.

Surface only liquids - Da, Fang; Hahn, David; Batty, Christopher; Wojtan, Christopher J; Grinspun, Eitan
We propose a novel surface-only technique for simulating incompressible, inviscid and uniform-density liquids with surface tension in three dimensions. The liquid surface is captured by a triangle mesh on which a Lagrangian velocity field is stored. Because advection of the velocity field may violate the incompressibility condition, we devise an orthogonal projection technique to remove the divergence while requiring the evaluation of only two boundary integrals. The forces of surface tension, gravity, and solid contact are all treated by a boundary element solve, allowing us to perform detailed simulations of a wide range of liquid phenomena, including waterbells, droplet and jet collisions, fluid chains, and crown splashes.

Efficiently computing data-independent memory-hard functions - Alwen, Joel F; Blocki, Jeremiah
A memory-hard function (MHF) f is equipped with a space cost σ and time cost τ parameter such that repeatedly computing fσ,τ on an application specific integrated circuit (ASIC) is not economically advantageous relative to a general purpose computer. Technically we would like that any (generalized) circuit for evaluating an iMHF fσ,τ has area × time (AT) complexity at Θ(σ2 ∗ τ). A data-independent MHF (iMHF) has the added property that it can be computed with almost optimal memory and time complexity by an algorithm which accesses memory in a pattern independent of the input value. Such functions can be specified by fixing a directed acyclic graph (DAG) G on n = Θ(σ ∗ τ) nodes representing its computation graph. In this work we develop new tools for analyzing iMHFs. First we define and motivate a new complexity measure capturing the amount of energy (i.e. electricity) required to compute a function. We argue that, in practice, this measure is at least as important as the more traditional AT-complexity. Next we describe an algorithm A for repeatedly evaluating an iMHF based on an arbitrary DAG G. We upperbound both its energy and AT complexities per instance evaluated in terms of a certain combinatorial property of G. Next we instantiate our attack for several general classes of DAGs which include those underlying many of the most important iMHF candidates in the literature. In particular, we obtain the following results which hold for all choices of parameters σ and τ (and thread-count) such that n = σ ∗ τ. -The Catena-Dragonfly function of [FLW13] has AT and energy complexities O(n1.67). -The Catena-Butterfly function of [FLW13] has complexities is O(n1.67). -The Double-Buffer and the Linear functions of [CGBS16] both have complexities in O(n1.67). -The Argon2i function of [BDK15] (winner of the Password Hashing Competition [PHC]) has complexities O(n7/4 log(n)). -The Single-Buffer function of [CGBS16] has complexities O(n7/4 log(n)). -Any iMHF can be computed by an algorithm with complexities O(n2/ log1 −ε(n)) for all ε > 0. In particular when τ = 1 this shows that the goal of constructing an iMHF with AT-complexity Θ(σ2 ∗ τ ) is unachievable. Along the way we prove a lemma upper-bounding the depth-robustness of any DAG which may prove to be of independent interest.

Provably robust sponge-based PRNGs and KDFs - Gazi, Peter; Tessaro, Stefano
We study the problem of devising provably secure PRNGs with input based on the sponge paradigm. Such constructions are very appealing, as efficient software/hardware implementations of SHA-3 can easily be translated into a PRNG in a nearly black-box way. The only existing sponge-based construction, proposed by Bertoni et al. (CHES 2010), fails to achieve the security notion of robustness recently considered by Dodis et al. (CCS 2013), for two reasons: (1) The construction is deterministic, and thus there are high-entropy input distributions on which the construction fails to extract random bits, and (2) The construction is not forward secure, and presented solutions aiming at restoring forward security have not been rigorously analyzed. We propose a seeded variant of Bertoni et al.’s PRNG with input which we prove secure in the sense of robustness, delivering in particular concrete security bounds. On the way, we make what we believe to be an important conceptual contribution, developing a variant of the security framework of Dodis et al. tailored at the ideal permutation model that captures PRNG security in settings where the weakly random inputs are provided from a large class of possible adversarial samplers which are also allowed to query the random permutation. As a further application of our techniques, we also present an efficient sponge-based key-derivation function (which can be instantiated from SHA-3 in a black-box fashion), which we also prove secure when fed with samples from permutation-dependent distributions.

Elementary approach to closed billiard trajectories in asymmetric normed spaces - Akopyan, Arseniy; Balitskiy, Alexey; Karasev, Roman; Sharipova, Anastasia (Proceedings of the American Mathematical Society)
We apply the technique of Károly Bezdek and Daniel Bezdek to study billiard trajectories in convex bodies, when the length is measured with a (possibly asymmetric) norm. We prove a lower bound for the length of the shortest closed billiard trajectory, related to the non-symmetric Mahler problem. With this technique we are able to give short and elementary proofs to some known results.

Cytokinins influence root gravitropism via differential regulation of auxin transporter expression and localization in Arabidopsis - Pernisová, Markéta; Prat, Tomas; Grones, Peter; Haruštiaková, Danka; Matonohova, Martina; Spíchal, Lukáš; Nodzyński, Tomasz; Friml, Jirí; Hejátko, Jan (New Phytologist)
Redirection of intercellular auxin fluxes via relocalization of the PIN-FORMED 3 (PIN3) and PIN7 auxin efflux carriers has been suggested to be necessary for the root gravitropic response. Cytokinins have also been proposed to play a role in controlling root gravitropism, but conclusive evidence is lacking. We present a detailed study of the dynamics of root bending early after gravistimulation, which revealed a delayed gravitropic response in transgenic lines with depleted endogenous cytokinins (Pro35S:AtCKX) and cytokinin signaling mutants. Pro35S:AtCKX lines, as well as a cytokinin receptor mutant ahk3, showed aberrations in the auxin response distribution in columella cells consistent with defects in the auxin transport machinery. Using in vivo real-time imaging of PIN3-GFP and PIN7-GFP in AtCKX3 overexpression and ahk3 backgrounds, we observed wild-type-like relocalization of PIN proteins in the columella early after gravistimulation, with gravity-induced relocalization of PIN7 faster than that of PIN3. Nonetheless, the cellular distribution of PIN3 and PIN7 and expression of PIN7 and the auxin influx carrier AUX1 was affected in AtCKX overexpression lines. Based on the retained cytokinin sensitivity in pin3 pin4 pin7 mutant, we propose the AUX1-mediated auxin transport rather than columella-located PIN proteins as a target of endogenous cytokinins in the control of root gravitropism.

Seed, expand and constrain: Three principles for weakly-supervised image segmentation - Kolesnikov, Alexander; Lampert, Christoph
We introduce a new loss function for the weakly-supervised training of semantic image segmentation models based on three guiding principles: to seed with weak localization cues, to expand objects based on the information about which classes can occur in an image, and to constrain the segmentations to coincide with object boundaries. We show experimentally that training a deep convolutional neural network using the proposed loss function leads to substantially better segmentations than previous state-of-the-art methods on the challenging PASCAL VOC 2012 dataset. We furthermore give insight into the working mechanism of our method by a detailed experimental study that illustrates how the segmentation quality is affected by each term of the proposed loss function as well as their combinations.

Correlation driven d wave superconductivity in Anderson lattice model: Two gaps - Wysokiński, Marcin; Kaczmarczyk, Jan; Spałek, Jozef (Physical Review B - Condensed Matter and Materials Physics)
Superconductivity in heavy-fermion systems has an unconventional nature and is considered to originate from the universal features of the electronic structure. Here, the Anderson lattice model is studied by means of the full variational Gutzwiller wave function incorporating nonlocal effects of the on-site interaction. We show that the d-wave superconducting ground state can be driven solely by interelectronic correlations. The proposed microscopic mechanism leads to a multigap superconductivity with the dominant contribution due to f electrons and in the dx2−y2-wave channel. Our results rationalize several important observations for CeCoIn5.

Drivers of structural features in gene regulatory networks: From biophysical constraints to biological function - Martin, Olivier; Krzywicki, André; Zagórski, Marcin P (Physics of Life Reviews)
Living cells can maintain their internal states, react to changing environments, grow, differentiate, divide, etc. All these processes are tightly controlled by what can be called a regulatory program. The logic of the underlying control can sometimes be guessed at by examining the network of influences amongst genetic components. Some associated gene regulatory networks have been studied in prokaryotes and eukaryotes, unveiling various structural features ranging from broad distributions of out-degrees to recurrent "motifs", that is small subgraphs having a specific pattern of interactions. To understand what factors may be driving such structuring, a number of groups have introduced frameworks to model the dynamics of gene regulatory networks. In that context, we review here such in silico approaches and show how selection for phenotypes, i.e., network function, can shape network structure.